Application of molasses improves strawberry marketability by enhancing fruit flavor and aroma - Yuanxiu Lin; Yu Long; Zimeng Cui; Siqi Dai; Yunting Zhang; Mengyao Li; Qing Chen; Yong Zhang; Haoru Tang; Yifei Zhou; Ya Luo (Postharvest Biology and Technology, 2026)

Cyclic regeneration and up-concentration for nitrate recovery from wastewater via in situ NaNO3 generation under saline, fully autotrophic nitrification conditions - Molin Lian; Zihang Ma; Guang Chen; Siqi Yu; Qing Xia; Bingjie Lin; Xiangdong Xu; Rui Tang; Zhen Zhou (Bioresource Technology, 2026)

MPP+ disorders Irg1-Itaconate axis to promote M1 polarization of microglia by activating succinate dehydrogenase - Lin-Yu Wang; Yi-Yun Tang; Wei Zou; Ping Zhang; Xiao-Qing Tang; Ping Zhang (Molecular Biology Reports, 2026)

Electric field optimizes bacterium-phage interactions to enhance biofilm adaptation and microbial function in constructed wetlands - Xiaohui Liu; Fengling Zhang; Zijun Lin; Tianci Tang; Jing Xu; Pingfeng Yu; Ying Liu; Fengchang Wu (Water Research, 2026)

Bioaccumulation, biotransformation and hormesis effects of 6PPD-Q in Eisenia fetida: Impacts on metabolism and gut microbiota - Lin Bian; Wenyan Yu; Hua Yin; Minghan Zhu; Shaoyu Tang; Jingtao Wu; Yuanyuan Yu (Journal of Environmental Sciences, 2026)

Deciphering the potential molecular links between ochratoxin A and colorectal cancer: an integrated computational toxicological and single-cell transcriptomic study - Tianqi Qiu; Junyi Zhuo; Hua Wu; Min Lin; Kaisheng Zhang; Yu Tang (Toxicon, 2026)

2(3→20)-abeo-taxoids with adipogenesis inhibitory activity from the leaves and twigs of Taxus chinensis var. mairei - Li-Ping Long; Xin-Yu Fan; Yuan-Hui Yu; Yuan-Liang Xu; Lin-Xi Mao; Xue Tang; Kai Guo; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Non-radical activation of peroxydisulfate by Fe-doped piggery digestate biochar for efficient sulfamethoxazole removal - Jiayi Li; Yunlong Wu; Qiqi Tang; Yuansheng Wang; Jiaqu Tan; Min Yu; Zhen Zhang; Zhixiao Lv; Yulong Zhang; Xueming Lin (Journal of Environmental Chemical Engineering, 2026)

Regional heterogeneity and vertical stratification of carbon dynamics in Chinese peatlands - Hui Zhang; Minna Väliranta; Angela Gallego-Sala; Zhan-Yi Lin; Chen-Yu Wang; Yan Zhao; Zheng-Tang Guo (Global and Planetary Change, 2026)

A high-throughput strategy for screening umami peptides from Chouguiyu based on peptidomics and machine learning-assisted molecular simulation - Sitong Lyu; Shichao Xuan; Fan Yang; Honglin Yu; Di Meng; Jianqing Zhou; Cristabelle De Souza; Zhe Zhang; Tongjie Liu; Huaxi Yi; Qingjuan Tang; Lanwei Zhang; et al. (Food Research International, 2026)

N-3 PUFA deposition and esterification patterns drive aroma profile remodeling in the longissimus dorsi of pigs fed flaxseed oil - Yingsen Liu; Longzhu Zhou; Luxi Lin; Shijie Wang; Yiyu Yin; Haoyang Han; Huihui Tian; Miaomiao Dong; Pingyang Li; Youyou Yang; Xiaohui Feng; Weihai Xing; et al. (Food Chemistry, 2026)

Structural characterization of novel polysaccharides from Sargassum fusiforme with dual anticoagulant activity targeting thrombin and antithrombin III - Yue Zhu; Yuanlin Luo; Yunqin Shi; Jiahui Shao; Shunhao Lin; Xiuting Zhang; Yu Tang; Xiangwei Zhao; Jianping Jiang; Zhenzhong Yang (Food Chemistry, 2026)

A tetrahedral framework DNA-metformin nano-firefighter for quenching adipose chronic inflammation: Reprogramming macrophages to restore metabolic homeostasis in obesity - Zhuo Chen; Jiaqi Li; Alimire Alifu; Fenglin Jiang; Wenjing Tang; Zaowei Yang; Yuhao Liu; Bo Tian; Xi Chen; Yu Chen; Qi Han; Yunfeng Lin (Chemical Engineering Journal, 2026)

Interannual variability of secondary organic carbon driven by seasonal shifts in formation regimes in southern Taiwan - Jun-Fa Ye; Chih-Yu Chan; Jian-Xian Wu; Shi-Ya Tang; Tse-Lun Chen; Li-Hao Young; Yu-Chieh Ting; Yen-Ping Peng; Wei-Hsiang Chen; Ming-Yeng Lin; Si-Chee Tsay; Neng-Huei Lin; et al. (Atmospheric Environment, 2026)

Visible-Light-Assisted Coagulation for Microcystis Removal: An Oxidant-Free route with Process-Safety Implications - Yu Chen; Fangyi Li; Yani Liu; Jie Yuan; Jiajia Wang; Lin Tang (Water, Air, & Soil Pollution, 2026)

Biodegradation of cyano liquid crystal monomers by an aerobic enrichment culture: Key degraders and interspecies synergistic mechanisms - Minghan Zhu; Chang He; Shaoyu Tang; Jiayu Zhang; Zhen Yu; Hui Lin; Yibo Yuan; Jonathan W.C. Wong; Hua Yin; Junfeng Niu; Xujun Liang; Zhi Dang (Water Research, 2026)

Intelligent monitoring and management of urban drainage systems through machine-learning-driven fusion of EEM and UV-Vis - Hao-Lin Yang; Xin Zhang; Shang-Wen Deng; Jia-Min Xu; Ruo-Zhou Lin; Zhi-Yu Zhang; Yu-Qi Wang; Ding-Ding Tang; Hong-Cheng Wang (Journal of Environmental Management, 2026)

Impact origin of pink spinel in the Chang’e-6 lunar soils - Linxi Li; Guangyuan Yu; Sen Hu; Hejiu Hui; Yi Chen; Qiu-Li Li; Wei Yang; Lihui Jia; Di Zhang; Shitou Wu; Guoqiang Tang; Hao Wang; et al. (Geochimica et Cosmochimica Acta, 2026)

Coupled effect of crack inclination and microstructure on the mechanical behavior of soils - Zhao-Lin Cai; Yu-Jun Cui; Chao-Sheng Tang; Qing Cheng; Zhi-Xiong Zeng; Xin-Lun Ji; Tao Wang; Hao Wang; Hai Wang; Jun-Feng Ren (Engineering Geology, 2026)

Dopamine-functionalized gel for rapid iodine and triiodide capture through adsorption-conversion pathway in aqueous media - Xinxin Li; Lin Jiang; Feng Lin; Zikang He; Rongzhi Tang; Yu Tan (Chemical Engineering Journal, 2026)

Tailored Cu active sites in 2D MOF-derived carbon nanosheets for dual electrochemical detection of chloramphenicol and paracetamol - Zhi-Lun Wu; Tsai-Ting Liu; Mei-Hong Tang; Sheng-Fei Lin; Yu-Jen Shih (Chemical Engineering Journal, 2026)

Unveiling the Impact of Copper Metabolism on Epithelial-Mesenchymal Transition of Triple-Negative Breast Cancer: Identification of Therapeutic Targets - Kai Zhuang; Lin Yan; Muhammad Waqas; Haixin Feng; Siqi Tang; Haoqi He; Xinshi Yu; Yanling Wang; Zunnan Huang (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Integrated multi-matrix bile acid metabolic metrics (BAMMs): A methodological framework for functional metabolic phenotyping in human subjects - Cheng-Hung Yang; Hsiang-Yu Tang; Chun-Ming Fan; Jui-Fen Lin; Mei-Ling Cheng (Analytica Chimica Acta, 2026)

The cortical morphology of cingulate cortex and microarchitecture of cingulum bundle correlate with cancer pain and anxiety in lung cancer patients - Lin Tang; Xiaosong Lan; Xiaoyu Zhou; Yu Tang; Jiahui Zheng; Junhao Huang; Yong Tan; Jing Zhang; Hong Yu; Meng Lin; Hua Lan; Xinying Ren; et al. (Brain Imaging and Behavior, 2026)

Metabolic rewiring and transcriptional interference underlie the biocontrol efficacy of Burkholderia arboris BB417 against Ralstonia solanacearum species complex - Shanwen Ding; Juan Zhang; Yang Wang; Guobing Lan; Lin Yu; Yafei Tang; Zhenggang Li; Bin Guo; Zifu He; Xiaoman She (Pesticide Biochemistry and Physiology, 2026)

Dynamic communication topology based formation control with double-loop controller for multiple AUVs - Wenkai Zhang; Min Yu; Haoyu Liu; Sheng Gao; Runda Lin; Qirong Tang (Ocean Engineering, 2026)

Unveiling the role of soil in urban vegetation greenness: City-scale evidence from field sampling across green spaces in Shanghai - Hanxin Tang; Mengyao Ci; Quanbo Yu; Shuyi Zhang; Ruoxi Lin; Junjie Ruan; Qicheng Zhong; Min Liu (Journal of Cleaner Production, 2026)

Development of a hydrazinolysis method for the determination of vinclozolin in foods by SPE and GC–MS/MS - Hongxia Tang; Yubo Li; Qinyi Sheng; Rui Yu; Dongwei Wang; Lin Ma; Guangyue Wen; Maofeng Dong; Xianbin Li; Li Zhao (Food Chemistry, 2026)

Breaking boundaries: A social–ecological network approach to collaborative governance of soil erosion risk - Yifan Lin; Jian Peng; Zihan Xu; Tao Hu; Xuebang Liu; Hui Tang; Shuying Yu (Ambio, 2026)

The Hippo–Yki pathway governs growth and cell fate in the posterior silk gland of the silkworm - Yan Ma; Zhiyong Zhang; Wenhui Zeng; Zhou Fang; Xin Yu; Lin Cheng; Zehui Ma; Qipeng Zeng; Dena Jiang; Yiyun Tang; Jie Hu; Chen Zhao; et al. (Insect Biochemistry and Molecular Biology, 2026)

Green and sustainable dual-pathway strategies for high-efficiency photoconversion of ergosterol to vitamin D₂ from agaricus bisporus - Jiahao Yu; Yan Tang; Yang Lin; Simin Feng; Mofei Shen; Ping Shao (Food Chemistry, 2026)

A food-derived octapeptide SRGQIEEL from yellow field pea protein hydrolysates inhibits xanthine oxidase via a tunnel-occlusion-like mechanism - Mei-Ling Li; Cheng-Hong Hsieh; Pei-Yu Wu; Shang-Ming Huang; Chung-Yu Tang; Yu-Shun Lin; Kuo-Chiang Hsu (Food Bioscience, 2026)

Magnolol disrupts membrane integrity and enhances colistin activity via a NagR-Mediated susceptibility in foodborne Aeromonas hydrophila - Xin Chen; Jinpeng Shi; Siyan Chen; Linbin Chen; Shuaiyuan Tang; Ruixiang Shi; Zhihan Yu; Wenbo Yu; Tianlong Lai; Yibin Liao; Liping Li; Xiangmin Lin (Food Bioscience, 2026)

Ultrasound-driven structural and functional modifications of grape seed protein revealed by power- and duration-dependent experiments - Ying-Yang Liu; Da-Rui Tang; Shi-Ling Wang; Wei-Wei Li; Jun-Wei Xu; Lian-Bing Lin; Yu-Hang Jiang; Qi-Lin Zhang (Food Hydrocolloids, 2026)

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

A novel UAV-based fusion of spectral and textural features with canopy stratification for accurate estimation of vertical nitrogen distribution in cotton - Guldana Sarsen; Qiu-xiang Tang; Ya-bin Li; Long-long Bao; Yu-hang Xu; Guang-yun Sun; Jian-wen Wu; Yierxiati Abulaiti; Qing-qing Lv; Fubin Liang; Na Zhang; Ren-song Guo; et al. (Computers and Electronics in Agriculture, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Dinemasone D — a new polyketide derivative with anti-inflammatory activity from Phaeosphaeria poagena - Li-Bin Lin; Jia-Hao Ning; Kang-Hong Zhao; Jia-Yao Hu; Guang-Yu Bai; Pan Deng; Shao-Qi Tang; Wen-Ke Dou; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2026)

Hierarchically assembled UiO-66@PIL@PP core-shell catalyst: Synergistic integration of catalysis and CO2 enrichment for efficient cycloaddition - Zhenzhu Tang; Qian Zhang; Baowen Lin; Yunliang Yu; Yanbin Zeng; Chao Zou; Guanqun Xie; Xiaoxia Wang (Journal of Environmental Chemical Engineering, 2026)

Enhancing environmental stress tolerance of Saccharomyces cerevisiae by deletion of NTH1 and FKS3: Implications for beer brewing - Chih-Yuan Tan; Huan-Yu Lin; Tsung-Tang Chen; Ying-Ta Shih; Yun-Chin Chung (International Journal of Food Microbiology, 2026)

A power-law relationship between bulk modulus and permeability in fractured sandstone: Insights from tidal analysis - Xu-Lin Tang; Xiao-Wei Jiang; Zhe-Ming Shi; Zhi-Yu Qi; De-Qiang Mao; Xu-Sheng Wang; Yan Zhang; Li Wan; Hong-Bin Yan (Engineering Geology, 2026)

Tailored self-assembled molecule for efficient charge extraction and enhanced crystallization in wide-bandgap perovskite solar cells - Haojun Hu; Xianglang Sun; Xuke Yang; Zongbao Li; Peiyan Zhang; Xinyu Yu; Shi'ang Li; Zifan Lin; Dayu Liu; Ziyang He; Chuyun Deng; Longhui Zeng; et al. (Chemical Engineering Journal, 2026)

Elucidating β-ocimene ozonolysis through combined experiments and theoretical calculations: The Criegee intermediate and peroxy radical pathways - Yu Xia; Xiaofeng Tang; Xiaoxiao Lin; Bo Long; Christa Fittschen; Weijun Zhang (Atmospheric Environment, 2026)

Key Parameters Prediction of Shale Reservoir Based on Deep-Learning Model: A Case Study of Jurassic Da’anzhai Member in Sichuan Basin - Wenqiang Tang; Chao Ma; Shengjian Zhou; Shaomin Zhang; Qiyu Wang; Kunyu Wu; Haitao Hong; Jiashan Lin; Yun Yang; Kai Yu (Journal of Earth Science, 2026)

Nanofiber engineering of covalent organic frameworks via monomer–solvent synergy for high-efficiency uranium capture - Xiao-yi Tang; Qun-yan Wu; Yi-chen Huang; Peng-fei An; Lin Wang; Ji-pan Yu; Shu-sen Chen; Zi-jie Li; Li-yong Yuan; Wang-suo Wu; Zhi-fang Chai; Wei-qun Shi (Journal of Hazardous Materials, 2026)

Application of layered double hydroxides (LDHs) derived catalysts for selective catalytic reduction of NOx with NH3 - Tian-yu Lv; Zuo-lin Cui; Rui-tang Guo (Fuel, 2026)

Casein-liposome complex loading basil essential oil: Preparation, antibacterial effect, and preservative effect on braised beef - Yunshuang Man; Hui Tang; Yudi Wang; Rongrong Yang; Dongling Yan; Qianqian Yu; Lang Zhang; Lin Mei; Jun Qi; Lele Shao (Food Chemistry, 2026)

Accelerated fermentation of traditional Ba-bao Douchi by bacterial inoculation: Metabolomic and microbial community insights - Jinge Li; Xiangna Lin; Daqiao Yang; Xiaojuan Tang; Jiaojiao Yu; Hongzhuan Yang; Yunguo Liu (Food and Humanity, 2026)

Analysis of the species distribution and drug resistance of pathogenic microorganisms causing diabetic foot infections in Southwest China from 2020 to 2024: a retrospective cross-sectional analysis - Shangyu Zhang; Junchi Chen; Rui Sun; Yu Pan; Yusen Zhuo; Li Tang; Jianhua Zhu; Shuyang Li; Lin Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Environmental PET-microplastic exposure and risk of non-alcoholic fatty liver disease: An integrated computational toxicology and multi-omics study - Yu Yuan; Chunli Lin; Tianyu Zhang; Chao Song; Yuewen Sun; Hongzhen Tang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

A mixed-fluid genetic model for the baiceng fluorite deposit, SW China: Deciphering the magmatic thermal driver and basinal fluid sources - Xi-Wen Zhang; Zhong-guo Jin; Ming-hong Zheng; Jun Chen; Ze-liang Yu; Long Luo; Yong-hu Su; Lin Ye; Yan-wen Tang; Min-shan Gun (Earth Science Informatics, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Ammonium oxalate-mediated synergistic engineering of pores and defects in boron nitride granule catalysts for high-efficiency oxidative desulfurization - Tiantian Deng; Jing Lin; Chao Yu; Zhonglu Guo; Chengchun Tang; Yang Huang (Journal of Hazardous Materials, 2026)

Thin film nanocomposite membrane incorporated with sulfonic acid-based HOFs for efficient reverse osmosis desalination - Yu-ting Liu; Zi-yue Tang; Zi-ao Zong; Wan-zhen Wang; Xiao-yin Zhang; Xin-ping Song; Xiang-min Meng; Rijia Lin; Jingwei Hou (Desalination, 2026)

Decoding the S/N ratio in sulfur autotrophic denitrification-partial denitrification (SAD-PD) systems: Bridging laboratory optimization to techno-economic feasibility - Xueyao Zhang; Xiangyu Peng; Jing Tang; Yu Chen; Jie Yuan; Lin Tang (Chemical Engineering Journal, 2026)

USP7 protects histone H1.2 from proteasome-mediated degradation to facilitate DNA repair and pancreatic neuroendocrine neoplasms progression - Mujie Ye; Lin Xu; Ping Yu; Jialing Pan; Xiaoting Shi; Bingyan Xue; Na He; Ping Hu; Min Liu; Xintong Lu; Yuemei Xu; Yanling Xu; et al. (Science China Life Sciences, 2026)

QSAR-enhanced machine learning for mechanistic insights and real-time prediction of DBPs in drinking water distribution systems - Dai-Xu Zhang; Tian-Yang Zhang; Zhen-Ning Luo; Zhu Peng; Zheng-Xiong Zheng; Yun-Qiao Zeng; Qi Fu; Ling Hu; Bing Geng; Chao-Yi Tong; Yu-Lin Tang; Bin Xu (Water Research, 2026)

Spatial patterns and environmental drivers of evapotranspiration across the Chinese Grassland Transect - Lexin Ma; Zhi Chen; Tianxiang Hao; Meng Yang; Quanhong Lin; Weikang Zhang; Lang Han; Zhaogang Liu; Mingyu Sun; Yong Lin; Xianjin Zhu; Shiping Chen; et al. (Journal of Hydrology, 2026)

Effect of protein–polyphenol interactions on the structural and digestive properties of pork myofibrillar proteins - Yu Chen; Qingyao Jiang; Yan Lu; Qiao Zeng; Ping Liu; Jiaxin Chen; Hongbin Lin; Jie Tang; Jie Zhao (Journal of Food Engineering, 2026)

Self-cleaning nanofiber membrane for efficient oil-water separation and dye degradation - Hai-chao Bai; Zi-yue Tang; Zi-ao Zong; Xin-ping Song; Yu-ting Liu; Xiaoyin Zhang; Xin-ping Wang; Xiang-min Meng; Rijia Lin; Jingwei Hou (Journal of Cleaner Production, 2026)

Significant suppression of sulfur–containing organic aerosols by emission controls during the Hangzhou Asian Games - Jintian Zhang; Lei Liu; Jianxiong Rong; Lin Du; Zechen Yu; Shanshan Tang (Journal of Environmental Sciences, 2026)

Multi-omics reveals efficient thiamethoxam biodegradation but altered flavor profile by native microbiota during Pixian broad bean paste fermentation - Xuan Yu; Siqi Huang; Jie Tang; Chuanning Peng; Qi Wen; Siqi Chen; Lanqi lei; Chenxi Yang; Yuanxi Liu; Wenliang Xiang; Qing Zhang; Hongbin Lin; et al. (International Journal of Food Microbiology, 2026)

Integrated targeted lipidomics and electronic nose analyses reveal lipid composition differences between chicken meat with varying fat levels and odor dynamics during cold storage - Zhongzhen Lin; Chunlin Yu; Donghao Zhang; Yuan Tang; Yufei Wang; Songhang Yu; Chaowu Yang; Yiping Liu (Food Chemistry, 2026)

Optoelectronic synaptic transistor array based on CsPbBr3/grating-patterned IDTBT heterojunctions for neuromorphic visual fatigue sensing - Jiajie Hong; Zhiqian Wei; Zunxian Yang; Yue Chen; Luxi Yuan; Shangwei Ye; Xudong Jiang; Yuting Bai; Benfang Liu; Zhiyu Yuan; Wenxin Zhang; Jie Li; et al. (Chemical Engineering Journal, 2026)

Multi-model machine learning framework for prediction of greenhouse gas emissions during composting of organic solid waste - Jing He; Jing Tang; Zhonghao He; Qiqi Fu; Yi Li; Ci Song; Wei Huang; Jiajia Wang; Jiangfang Yu; Lin Tang (Bioresource Technology, 2026)

Spatiotemporal variations in indoor thermal environments and dynamic comfort of passengers in airport terminals during winter - Yuxin Yang; Juan Yu; Deyin Zhang; Hao Tang; Wenzhong Jiang; Libin Han; Junmin Li; Borong Lin; Yu Dong (Building and Environment, 2026)

Untargeted lipidomic profiling reveals the effect of hexabromocyclododecane exposure on a branching coral - Chuan-Ho Tang; Ting-Ju Liu; Ching-Yu Lin; Hsing-Hui Li (Aquatic Toxicology, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Coping or not? A stackelberg game perspective on European Union strategies for the rising Chinese electric vehicle market share - Yu Lin; Minghui Liu; Tieqiao Tang; Na Yan; Dongxu Chen (Journal of Cleaner Production, 2026)

A microenvironment-responsive chitosan based injectable hydrogel with synergistic anti-inflammatory effects of triptolide and copper ions for spinal cord injury repair - Han-Jian Hu; Zhenming Tian; Zeng-Lin Li; Chun Cheung Chan; Hongyan Zhang; Shipeng Tang; Yu Chen; Zhaoyin Chen; Tian Hu; Bin Liu; Gang-Biao Jiang (Carbohydrate Polymers, 2026)

Soil calcium ion enrichment associated with altered microbial functional gene networks in bamboo forest expansion - Yaoxing Wu; Huimin Tian; Jiahuan Guo; Yawen Shen; Qingqing Liu; Lin Yu; Zhiyin Tang; Yihang Jia; Gong Zhang; Jun Deng; Lianghua Qi (Applied Soil Ecology, 2026)

Caffeoylquinic acid derivatives (CQAs) from Daphne gemmata and their antimicrobial activities - Lin Li; Fu-Qiang Song; Ping-Jing Yu; Li-Ping Tang; Xian Li (Natural Product Research, 2026)

Optical properties of dissolved organic matter play pivotal roles in mediating trace metal forms in a mangrove-dominated tidal estuary - Keisuke Nakayama; Meng-Chi Hung; Chih-Yu Chiu; Sen-Lin Tang; Mei-Li Hsueh; Chin-Ching Wu; I-Hao Hung; Ya-Hsin Liu; Jeng-Wei Tsai (Marine Pollution Bulletin, 2026)

Dicyanoisophorone-based near-infrared fluorescent probe with a large Stokes shift for the detection and bioimaging of hydrazine - Hong-Cheng Xia; Yu-Hang Zhang; Li-Ming Lv; Di Han; Hong-Kun Yang; Hui-Juan Yan; Jie-Li Lv; Jun-Tang Lin; Ying-Ying Kong (Journal of Hazardous Materials, 2026)

Dibifree, a dietary phytomix, improves glycemic control and adiposity via modulation of the gut–pancreas–adipose–immune axis in type 2 diabetes - Tzu-Yi Huang; Niann-Tzyy Dai; Hsiu-Jung Liao; Ly Hien Doan; Tai-Shan Cheng; Wen-Yu Hsieh; I-Hsuan Lin; Yu-Tang Huang; Chia-Ching Liaw; Hsiao-Sheng Liu; Wei-Ming Cheng; Chun-Li Su; et al. (Food Research International, 2026)

Unveiling the metabolic mechanism of pesticide in food fermentation through metagenomics and metabolomics: A case study of β-cypermethrin in Pixian broad-bean paste - Siqi Huang; Xuan Yu; Jie Tang; Chuanning Peng; Qi Wen; Siqi Chen; Lanqi lei; Chenxi Yang; Yuanxi Liu; Wenliang Xiang; Qing Zhang; Hongbin Lin; et al. (Food Chemistry, 2026)

Electroactivated cobalt-cobalt Prussian blue analog composite membrane for rapid persulfate-driven antibiotic degradation and fouling mitigation - Xiaoyue Yao; Hao Wang; Jingjing Liu; Yu Wang; Xuewen Tang; Hongjun Lin; Leihong Zhao; Bisheng Li; Renjie Li (Chemical Engineering Journal, 2026)

Hippocampal Neuronal Ferroptosis Driven by Lipocalin-2 Mediates Comorbid Visceral Pain and Anxiety in Irritable Bowel Syndrome - Ying Tang; Zhengqing He; Qianli Zhang; Yiqian Liu; Lu Li; Yu Chen; Aiqin Chen; Chun Lin (Molecular Neurobiology, 2026)

The formation of autophagosomes in the development process of rice endosperm is affected by endogenous ascorbic acid - Le Yu; Mengwei Chen; Haoran Yan; Zeliang Ouyang; Xinyu Liu; Sitong Lin; Yixuan Tang; Zhipeng Xu; Chunyu Liu; Peiyi Chen; Liping Zhou; Yonghai Liu (Acta Physiologiae Plantarum, 2026)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

First report of Thraustochytrium caudivorum isolated from the undulated surf clam (Paratapes undulatus): Morphological, molecular, and ecological insights under climate change - Yu Chen; Seung-Hyeon Kim; Jinxia Long; S.D.N.K. Bathige; Hyoun Joong Kim; Sen-Lin Tang; Kyung-Il Park (Protist, 2025)

Potential anti-H1N1 schitriterpenoids from Kadsura japonica L. vines - Hung-Tse Huang; Chun-Tang Chiou; Yu-Chi Lin; Li-Jie Zhang; Chih-Hua Chao; Ping-Jyun Sung; Jih-Jung Chen; Tsung-Lin Li; I-Wen Lo; Chia-Ching Liaw (Phytochemistry, 2025)

Magnetic mineral dissolution front delimited by late Holocene sediment accumulation acceleration in the inner shelf, northern South China Sea - Mingkun Li; Meng Tang; Liang Chen; Yongying Zeng; Rou Wen; Junyu Lin; Mingjie Yu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Serum copper-zinc and copper-selenium ratios in relation to bone health among U.S. adolescents - Yanfang Shen; Haobiao Liu; Yuwen Shangguan; Qingsong Li; Xuefeng Yu; Huiyan Tang; Xue Lin (Journal of Trace Elements in Medicine and Biology, 2025)

Revealing the polyphenol modulation mechanism for in vitro gastric digestion properties of myofibrillar proteins via noncovalent interaction - Yan Lu; Chaoqun Chen; Yu Chen; Shuaiqian Wang; Yanping Hu; Ping Liu; Hongbin Lin; Jie Tang; Jie Zhao (Food Chemistry, 2025)

Synergistic exposure to endocrine-disrupting chemicals in pediatric lungs: Epidemiological drivers and disease-associated variations - Chunzhao Chen; Jie Yu; Hui Qi; Cuiying Zhong; Jian Tang; Chenghao Chen; Zheng Li; Xuemei Yang; Yujia Wu; Wanning Chen; Gang Yu; Lin Sun (Environmental Pollution, 2025)

Dissolving microneedles loaded with Acanthopanax Senticosus-derived vesicles and PEI for antibacterial activity, cfDNA scavenging, anti-inflammation, and angiogenesis in diabetic wounds - Huiling Ye; Junze Tang; Wanting Liang; Yushan Li; Zhaoyi Ye; Jiasen Lin; Guining Cao; Yaoxun Zeng; Yu Sun; Meijing Wang; Ziqiao Li; Xin Cheng; et al. (Chemical Engineering Journal, 2025)

Self-healing, highly stretchable, recyclable PU-curcumin elastomer with substrate-sensitive solid-state fluorescence - Linjie Wei; Xiubin Xu; Hongchun Mu; Wantong Lin; Jiahui Tang; Jieran Li; Jianwei Liu; Haitao Dong; Danfeng Yu; Xu Wu (Chemical Engineering Journal, 2025)

Effects of gum incorporation on the properties of sodium alginate-based composite hydrogel beads for encapsulating lactic acid bacteria - Ying-Ying Jing; Yun-Cheng Li; Yong-Qi Luo; Long-Hua Zou; Yuan-Mou Tang; Yu-Xi Lin; Fan-Bing Meng (Carbohydrate Polymers, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Early hyperferritinemia in polytrauma: a biomarker of systemic inflammation and mortality risk in a multicenter cohort study - Shunyao Chen; Teding Chang; Jialiu Luo; Cong Zhang; Peidong Zhang; Shuaipeng Gu; Zhiqiang Lin; Yujie Chen; Youxie Shen; Liming Dong; Qian Wan; Liang He; et al. (Inflammation Research, 2025)

Histological studies on the ontogeny of the big-belly seahorse (Hippocampus abdominalis) - Yuanyuan Xue; Lu Tang; Chunhui Lv; Fang Wang; Xiaolei Su; Mingzhu Li; Yuping Hou; Jie Dong; Chengde Fan; Jiezhou Wang; Lin Shi; Qunhao Zhou; et al. (Fish Physiology and Biochemistry, 2025)

Comprehensive overview: QuEChERS methods for mycotoxin determination in different matrices - Ruifeng Lin; Jiandan Yuan; Huiqiang Feng; Yanling Liu; Yu Fan; Yuzhu Tan; Zhentao Tang (Food Additives & Contaminants: Part A, 2025)

Product and mechanistic insights into the oxidation of cyclohexane via synchrotron radiation vacuum ultraviolet photoionization mass spectrometry - Xiaoxiao Lin; Lingyu Liu; Yu Xia; Zuoying Wen; Christa Fittschen; Wei Liu; Milán Szőri; Béla Fiser; Zhandong Wang; Xiaofeng Tang (Science of The Total Environment, 2025)

Underlying mechanism of sucrose esters on myofibrillar protein O/W emulsion gel behaviour under different ionic strengths: Focus on emulsion characterisation, protein structural changes and molecular interactions - Xiang Li; Bo Wang; Wenwen Hou; Jie Tang; Hongbin Lin; Junqiang Lian; Qian Liu; Mingfeng Xu; Yuan Ma; Dong Yu; Dong Zhang; Jiaxin Chen (Food Chemistry, 2025)

Product and mechanistic insights into the ozonolysis of Δ3-Carene - Xulian Song; Xiaoxiao Lin; Yu Xia; Ziji Ma; Liqin Jin; Weijun Zhang; Zhandong Wang; Christa Fittschen; Xiaofeng Tang (Atmospheric Environment, 2025)

Atmospheric nitrogen deposition to cropland in Fujian province, China - Ziyin Yu; Mengjuan Han; Zhang Wen; Wenqing Li; Changzheng Wu; Xin Ma; Wen Xu; Ruotong Si; Xiaoping Xia; Aohan Tang; Lin Zhang; Goulding Keith; et al. (Atmospheric Environment, 2025)

System characteristics of integrated continuous flow simultaneous partial Nitrification, Anammox and Denitrification (SNAD) for NH4+-rich wastewater: performance, sludge evolution, metagenomic sequencing analysis - Peng-fei Yu; Ding Wang; Xing-guan Ma; Yu-bo Fu; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Dong-xue Li; Xing Jin; Kang-da Yang; Li-cheng Zhang; et al. (Environmental Research, 2025)

Microwave-extracted insect melanin as a metal chelator for bimetallic bioelectro-fenton cathodes: A sustainable approach to ibuprofen-contaminated wastewater treatment - Shu-Hui Liu; Hui-Yu Tang; Chi-Wen Lin; Wei-Jun Lai (Chemical Engineering Journal, 2025)

Synergistic band structure tailoring and texturing enhance cooling-power generation Bifunctionality in Bi0.4Sb1.6Te3 - Lin Liao; Jingjing Cui; Keke Liu; Xili Wen; Xingyan Dong; Ming Liu; Ding Luo; Yu-Ke Zhu; Xianli Su; Jiehe Sui; Jinsong Wu; Xinfeng Tang (Chemical Engineering Journal, 2025)

Aqueous photochemistry of brown carbon: H2O2 formation, enhanced SO2 oxidation, and the real role of excited triplets - Beibei Liu; Lingdong Kong; Yixuan An; Yu Lu; Yuwen Wang; Jie Tan; Xingfu Tang; Lin Wang (Atmospheric Environment, 2025)

A precisely regulated Streptomyces expression system pTZYp facilitated by the strong promoter stnY and cmt operon - Kai Zhang; Ao-yu Wang; Qiang Zhou; Yi-feng Chen; Shuang-jun Lin; Gong-li Tang (Biotechnology Letters, 2025)

Unveiling Unusual Ecofunctional Traits of Endozoicomonas Species Through Comprehensive Comparative Genomics - Sim Lin Lim; Ching‐Hsiang Chin; Yu‐Jing Chiou; Ming‐Tsung Hsu; Pei‐Wen Chiang; Hsing‐Ju Chen; Yung‐Chi Tu; Wen‐Shyong Tzou; Sen‐Lin Tang (Environmental Microbiology, 2025)
Endozoicomonas is an omnipresent marine bacterial genus, associated with various marine organisms, that contributes to host health, nutrient cycling and disease resistance. Nonetheless, its genomic features remain poorly characterised due to a paucity of high‐quality genomes. In this study, we sequenced 5 novel Endozoicomonas strains and re‐sequenced 1 known strain to improve genomic resolution. By integrating these 6 high‐quality genomes with 31 qualified published genomes, our pan‐genomic analysis revealed variation in genetic traits among clades. Notably, Endozoicomonas lacks quorum‐sensing capabilities, suggesting resistance to quorum quenching mechanisms. It also lacks the capacity to synthesise and transport vitamin B12, indicating that it does not supply this nutrient to holobionts. Remarkably, Endozoicomonas genomes encode 92 identified giant proteins (15–65 kbp). These proteins cluster into three major groups associated with antimicrobial peptide synthesis, exotoxin production and cell adhesion. Additionally, we found that Endozoicomonas has acquired prophages from diverse sources via infection or other types of gene transfer. Notably, CRISPR‐Cas sequences suggest evolutionary trajectories independent of both prophage acquisition and phylogenetic lineage, implying potential geographic influences or environmental pressures. This study provides new insights into the genomic diversity of Endozoicomonas and its genetic adaptations to diverse hosts.

Numerical Analysis of Thermal–Structural Coupling for Subsea Dual-Channel Connector - Feihong Yun; Yuming Du; Dong Liu; Xiaofei Wu; Minggang Tang; Qiuying Yan; Peng Gao; Yu Chen; Xu Zhai; Hanyu Sun; Songlin Zhang; Shuqi Lin; et al. (Journal of Marine Science and Engineering, 2025)
In deep-sea oil and gas development scenarios, deep-sea dual-channel connectors often face the risk of seal failure due to internal and external temperature difference loads. To address this issue, this paper systematically establishes equivalent heat transfer models for the key parts of the connector based on the third-type boundary condition. On this basis, the quantitative correlation between the equivalent thermal conductivity, composite heat transfer coefficient and temperature of each part is explored. Using the finite element numerical simulation method, the transient temperature field of the connector under three working conditions (heating, cooling and temperature shock) is simulated and analyzed, revealing the temperature distribution characteristics and temperature change trends of the maximum temperature difference of each key component of the connector; combined with thermal–structural coupling simulation, the temperature field is converted into static load, to determine the behavior of the contact stress on the sealing surface under different temperature–pressure coupling working conditions; in addition, by placing the test prototype in a high-low temperature cycle chamber, the seal performance tests under pressurized and non-pressurized working conditions are carried out to verify the reliable sealing performance of the connector under variable temperature conditions. The results of this paper provide comprehensive theoretical support and an experimental basis for the thermodynamic optimization design of deep-sea connectors and the improvement of the reliability of the sealing system.

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Enhancement of Bacillus subtilis inactivated Microcystis aeruginosa by shaped biochar: Performance and mechanism study - Aoxue Yu; Qili Peng; Dawei Zhou; Jiangfang Yu; Naif Abdullah Al-Dhabi; Bo Peng; Yanzhong Tan; Wangwang Tang; Lin Tang (Journal of Hazardous Materials, 2025)

Sustainable aviation fuel and next-generation aircraft: Low-carbon pathway for China's civil aviation industry - Rui Yan; Bao-Jun Tang; Yu-Jie Hu; Chang-Jing Ji; Kun-Ben Lin; Meng Shen (Journal of Environmental Management, 2025)

“Zombie” cell drug delivery system: A novel strategy for the treatment of cancer and inflammation-related diseases - Zhouru Wang; Wenjing Yang; Danhua Liu; Peihong Lin; Rui Gao; Zhen Ma; Qiao Wang; Zhan Tang; Jie Fang; Wenying Yu (Chemical Engineering Journal, 2025)

Self-cleaning nanofiber membranes for sustainable dual removal of oils and dyes from wastewater - Hai-chao Bai; Yu-kun Sun; Zi-yue Tang; Zi-ao Zong; Yu-ting Liu; Xiaoyin Zhang; Xin-ping Wang; Xiang-min Meng; Jingwei Hou; Rijia Lin (Chemical Engineering Journal, 2025)

Enhancing medium-chain-length polyhydroxyalkanoate (mcl-PHA) synthesis in mixed microbial cultures via targeted substrate composition: A meta-omics guided approach - Shihan Huang; Mier Wang; Jie Yuan; Yu Chen; Lin Tang (Bioresource Technology, 2025)

Nitrogen addition improved rhizosphere phosphorus availability and phosphorus-phytoextraction of Polygonum hydropiper through optimizing rhizosphere enzymes, microbial interactions and functions - Daihua Ye; Xiaoyu Bai; Min Xie; Yujie Li; Tao Liu; Lin Ji; Xizhou Zhang; Huagang Huang; Haiying Yu; Yu Tang; Yongdong Wang; Tingxuan Li (Plant and Soil, 2025)

Soil microbial community harboring key genes drives rhizosphere phosphorus mobilization of phosphorus-accumulating Polygonum hydropiper - Daihua Ye; Yuyue Lin; Tao Liu; Xizhou Zhang; Yu Tang; Keji Wang; Huagang Huang; Haiying Yu; Yongdong Wang; Xinhua He; Tingxuan Li (Applied Soil Ecology, 2025)

Two new chemical constituents from the aerial parts of Tripterygium wilfordii - Xia Zhang; Lei Huang; Yu-Jun Tang; Ya-Lin Hu; Wei Xu; Hong-Yu Li; Yu-Bo Zhang; Xiao-Qi Zhang; Guang-Xiong Zhou (Natural Product Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

A stable dual-functional monomer imprinted polymer platform for electrochemical sensitive detection of PFAS - Xingyang Cheng; Jing Tang; Yu Chen; Xue Bai; Yibo Liao; Xilian Ouyang; Yuchen Wang; Lin Tang (Journal of Hazardous Materials, 2025)

On-site tracking of trace Aflatoxin B1 in food waste composting via a portable colorimetric sensing platform with nanozymes - Yating Lu; Fuqing He; Xu Zhu; Jing Tang; Yue Lu; Jiajia Wang; Jiangfang Yu; Li Chen; Xingyang Cheng; Tianhao Liu; Lin Tang (Journal of Hazardous Materials, 2025)

CD39 activities in the treated acupoints contributed to the analgesic mechanism of acupuncture on arthritis rats - Yu-Jia Li; Jie Lin; Si-Qi Tang; Wei-Min Zuo; Guang-Hong Ding; Xue-Yong Shen; Li-Na Wang (Purinergic Signalling, 2025)

Recommendations of Stable Mg, Si, V, Fe, Cu, Zn, Rb, Sr, Ag, Cd, Ba, and U Isotope Compositions for Multiple Geological References - Jinting Kang; Xuqi Chen; Xi Deng; Yuan Fang; Haichuan Jiang; Chengyihong Liu; Cuihua Luo; Xing Li; Yuchao Lin; Zhaoqi Ren; Jiaru Sheng; Xue Tang; et al. (Journal of Earth Science, 2025)

Dual-stage matrix elimination-ICP-MS methodology for REEs profiling in barite-associated ores - Xue-lin Dong; Jun-han Liu; Zheng-xun Jia; Shao-zhan Tang; Shuo-yun Tong; Yu-xiang Xiong; Lei Ouyang (Analytica Chimica Acta, 2025)

Amino-functionalized MIL-101(Fe)-NH2 as efficient peracetic acid activator for selective contaminant degradation: Unraveling the role of electron-donating ligands in Fe(IV) generation - Renjie Pan; Zongchen Li; Tian-Yang Zhang; Qi Fu; Zheng-Xiong Zheng; Jun Shi; Jian Lu; Chen-Yan Hu; Yu-Lin Tang; Mohamed Gamal El-Din; Bin Xu (Journal of Hazardous Materials, 2025)

Innovative immunosonogen nanoplatform combining sonodynamic oxygenation and immunomodulation for superior cancer therapy - Jiali Tang; Yanlu Chen; Hao Lai; Qi Zeng; Yu Li; Junqi Feng; Ningjing Lin; Ronghua Jin; Junjie Liu; Tao Luo; Zixuan Liang (Chemical Engineering Journal, 2025)

Nitrogen level determines arbuscular mycorrhizal fungi nitrogen uptake rate of Stipa purpurea in alpine steppe - Jiahui Sun; Yu Tang; Keyu Chen; Shijie Ren; Hailan Shi; Qiang Dong; Junfu Dong; Lin Zhang; Xiaoyong Cui; Yanfen Wang; Baoming Ji; Jing Zhang (Plant and Soil, 2025)

Mechanistic insights into endometriosis: roles of Streptococcus agalactiae and L-carnitine in lesion development and angiogenesis - Yuan Zhuang; Ting Lyu; Yang Chen; Wei Li; Lei Tang; Shi-ping Xian; Peng-fei Yang; Lijie Wang; Qian-qian Zhang; Chaoming Mei; Yu-jing Lin; Zhixiang Yan; et al. (Angiogenesis, 2025)

Alternating electric field as an effective inhibitor of bioavailability and phytotoxicity of heavy metals during electric field-assisted aerobic composting - Tao Fu; Chang Shen; Huan Mi; Jiahuan Tang; Long Li; Hao Lin; Huayuan Shangguan; Zhen Yu (Journal of Hazardous Materials, 2025)

Electric field-assisted aerobic composting: From basic principles to applications - Tao Fu; Huan Mi; Chang Shen; Shuqun Zhang; Huayuan Shangguan; Jiahuan Tang; Hao Lin; Zhen Yu (Journal of Environmental Management, 2025)

Ultrastructure and sense organs of ovipositors in the phytophagous gall-maker pest Ophelimus maskelli (Hymenoptera: Eulophidae) and its parasitoid, Closterocerus chamaeleon (Hymenoptera: Eulophidae) - Yuan-Hao Li; Yu-Yue Huang; Yu-Chun Huang; Xiao-Rong Tang; Wen-Ting Huang; Xia-Lin Zheng (Journal of Asia-Pacific Entomology, 2025)

A vertical reverse zoning in the Kunshan W-Mo-Cu deposit, South China: Insights from mineral paragenesis, zircon geochemistry and S-Pb-O isotopes - Qingqing Yin; Juxing Tang; Qiuming Pei; Inna Safonova; Xinkui Xiang; Jingjing Dai; Aorigele Zhou; Bin Lin; Yumin Xu; Zhendong Yu; Jinling Xie; Ruihua Lin; et al. (Gondwana Research, 2025)

A multifunctional metformin loaded carboxymethyl chitosan/tannic acid/manganese composite hydrogel with promising capabilities for age-related bone defect repair - Jingle Chen; Chao Xie; Yucong Li; Qili Sun; Fengnian Yu; Kai Li; Haotian Gao; Zhaoquan Liang; Bin Tang; Lijun Lin (Carbohydrate Polymers, 2025)

Chemical constituents from the aerial parts of Clematis peterae - Pan-Pan Yu; Meng-Ya Chen; Ya-Ru Wu; Yong-Qi Guo; Ying-Zhen Tang; Zi-Han Zhu; Yang-Yang Ma; Shi-Hui Qian; Nan Yao; Zhen-Lin Li (Biochemical Systematics and Ecology, 2025)

An autocorrelation-based residual-stacking approach for GNSS multipath and diffraction mitigation and its application in high mountainous areas - Yumiao Tian; Wenhao Xiong; Yibing Liang; Yu Tang; Xi Mei; Xuefeng Yang; Miao Lin (Journal of Geodesy, 2025)

Contrasting responses of flowering phenology in C 3 and C 4 plants shape grassland community structure under global change - Lu Bai; Guodong Han; Lin Jiang; Thomas W. Crowther; Constantin M. Zohner; Kailiang Yu; Zhuwen Xu; Zhongwu Wang; Qian Wu; Yi Zhu; Jinglei Tang; Haiyan Ren (Ecology, 2025)
Climate change is known to affect plant phenology. Yet, the sensitivity of flowering phenology in dryland regions to climate change, and the potential implications for community composition, remain largely unexplored. Here, we used an 18‐year field experiment to investigate the effects of climate warming and nitrogen addition on flowering phenology of four C 3 plant species and two C 4 plant species, and the cascading effects on the relative abundance of C 3 and C 4 plants in a desert steppe. Across the past 10 years of the experiment (2013–2022), we found that warming had a greater effect on phenological shifts in C 3 than in C 4 plants. Warming significantly advanced the flowering time of C 3 plants by 4.3 ± 0.1 days and of C 4 plants by 2.8 ± 0.1 days, respectively. Warming also reduced the duration of flowering by 1.8 ± 0.1 days for C 3 plants but had no effect on C 4 plants, and decreased the dominance of C 3 plants compared to C 4 plants. Nitrogen addition extended the duration of flowering of C 4 plants by 3.4 ± 0.2 days and increased their relative dominance, while decreasing the dominance of C 3 plants. Structural equation models revealed that these phenological responses were largely driven by soil temperature and soil water availability. Our results demonstrate that the different phenological responses of C 3 and C 4 plants contribute to shifts in dominance between these plant types in temperate dryland ecosystems under global changes.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Five undescribed chromone-phenylpyridone hybrids from Cineraria repanda-derived Penicillium oxalicum with cytotoxic and antibacterial activity - Yu Wei Huang; Jing Guan; Yin Tang; Ren Xiang Tan; Li Ping Lin (Phytochemistry, 2025)

Polystyrene microplastics attenuated the impact of perfluorobutanoic acid on Chlorella sorokiniana: Hetero-aggregation, bioavailability, physiology, and transcriptomics - Zhilin Zhao; Xiaoying Zheng; Yue Li; Zongshuo Han; Yu Tang; Tianxing Hu; Tao Lin (Journal of Hazardous Materials, 2025)

Study on the nitrogen migration of different biomass by activated carbon-based MOF catalyst in hydrothermal environment - Gui-zhong Deng; Xiao-dong Tang; Jing-jing Li; Lin-yu Zhang; Zhi Yang; Fu-xiang Yang (Fuel, 2025)

Preparation of a polysulfone loose nanofiltration membrane with gradient structure via hybrid-induced phase separation for the efficient separation of dyes/salts - Yuanhui Tang; Huifang Yu; Yuwenyao Zhang; Juan Liu; Jihao Zhu; Yakai Lin; Hedi Chen; Yanping Hu; Jianqing Zhang; Song Hu; Hai Xie; Lixin Yu; et al. (Desalination, 2025)

Enhancing occupant-centric ventilation control in airport terminals: A predictive optimization framework integrating agent-based simulation - Hao Tang; Juan Yu; Yang Geng; Xue Liu; Zujian Huang; Yuren Yang; Zhe Wang; Ying Chen; Borong Lin (Building and Environment, 2025)

Experimental Study of the Hydrodynamic Forces of Pontoon Raft Aquaculture Facilities Around a Wind Farm Monopile Under Wave Conditions - Deming Chen; Mingchen Lin; Jinxin Zhou; Yanli Tang; Fenfang Zhao; Xinxin Wang; Mengjie Yu; Qiao Li; Daisuke Kitazawa (Journal of Marine Science and Engineering, 2025)
The integrated development of offshore wind power and marine aquaculture represents a promising approach to the sustainable utilization of ocean resources. The present study investigated the hydrodynamic response of an innovative combination of a wind farm monopile and pontoon raft aquaculture facilities (PRAFs). Physical water tank experiments were conducted on PRAFs deployed around a wind farm monopile using the following configurations: single- and three-row arrangements of PRAFs with and without a monopile. The interaction between the aquaculture structure and the wind farm monopile was examined, with a particular focus on the mooring line tensions and bridle line tensions under different wave conditions. Utilizing the wind farm monopile foundation as an anchor, the mooring line tension was reduced significantly by 16–66% in the single-row PRAF. The multi-row PRAF arrangement experienced lower mooring line tension in comparison with the single-row PRAF arrangement, with the highest reduction of 73%. However, for the bridle line tension, the upstream component was enhanced, while the downstream one was weakened with a monopile, and they both decreased in the multi-row arrangement. Finally, we developed numerical models based on flume tank tests that examined the interactions between the monopile and PRAFs, including configurations of a single monopile, along with single- and three-row arrangements of PRAFs. The numerical simulation results confirmed that the monopile had a dampening effect on the wave propagation of 5% to 20%, and the impact of the pontoons on the monopile was negligible, implying that the integration of aquaculture facilities around wind farm infrastructure may not significantly alter the hydrodynamic loads experienced by the monopile.

Coral incorporating microplastics leads to a health-risking immunometabolic shift - Chuan-Ho Tang; Ching-Yu Lin; Hsing-Hui Li (Chemosphere, 2025)

Cooperation of Lactoplantibacillus plantarum and polyethylene microplastics facilitated the disappearance of tetracycline during anaerobic fermentation of whole plant maize - Yubo Zhang; Pan Wang; Yu Tang; Chaosheng Liao; Xiaolong Tang; Pai Hou; Cheng Chen; Xiaokang Huang; Guangrou Lu; Lin Li; Mingjie Zhang; Fuxiang Li; et al. (Journal of Hazardous Materials, 2025)

Insights into algae cell inactivation by mixed chlor(am)ines in source water: Unraveling removal mechanisms, derived risks and control methods - Zhu Peng; Tian-Yang Zhang; Qi Fu; Xiang-Chi Xie; Zhen-Ning Luo; Yu-Lin Tang; Huan He; Chao Zeng; Jian Lu; Yun-Qiao Zeng; Chen-Yan Hu; Bin Xu (Journal of Environmental Chemical Engineering, 2025)

Investigating the main contributors to esterification activity and identifying the aqueous-phase ester synthases in Daqu - Yu Tie; Lin Wang; Bo Ding; Zhao Deng; Qian Yang; Min Zhu; Zhengyun Wu; Lan Tang; Taikei Suyama; Wenxue Zhang (Food Bioscience, 2025)

Catalyst pre-diffusion: An efficient strategy for the construction of COF nanofiltration membranes - Lin Yu; Aida Aibulatova; Zhen-Liang Xu; Li Li; Changqing Hao; Rui Jia; Yin-Xin Fang; Yan Zheng; Yong-Jian Tang (Desalination, 2025)

Iron-carbon amendment enhanced pollutant removal and greenhouse gas reduction in constructed wetlands under PFBA stress - Jiaqing Tao; Xiaoying Zheng; Chao Zhou; Zhilin Zhao; Tianxing Hu; Yi Fan; Yu Tang; Rui Wang; Tao Lin (Chemical Engineering Journal, 2025)

Association of residential greenness and sleep duration in adults: A prospective cohort study in China - Jiayi Li; Yaoyao Lin; Zongming Yang; Joachim Heinrich; Tianyu Zhao; Zhebin Yu; Wenqing Wang; Kaixuan Yang; Peng Shen; Hongbo Lin; Liming Shui; Jianbing Wang; et al. (Environmental Research, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Advancements in rapid on-site detection of chemical oxygen demand: Insights into sensing mechanisms and practical applications - Xingyang Cheng; Jing Tang; Yu Chen; Yibo Liao; Zhigang Yi; Pansong Li; Lin Tang (Chemical Engineering Journal, 2025)

Synthesis of phosphorylated covalent organic frameworks with different linkages–Critical factors controlling the extraction of uranium from highly acidic media - Xiao-Yi Tang; Hui-Di Zhang; Zi-Jie Li; Shuai Wang; Si-Yan Liu; Tao-Yuan Xiu; Ji-Pan Yu; Lin Wang; Li-Yong Yuan; Wang-Suo Wu; Wei-Qun Shi (Chemical Engineering Journal, 2025)

Bayesian-based Full Waveform Inversion - Huai-shan Liu; Yu-zhao Lin; Lei Xing; He-hao Tang; Jing-hao Li (Applied Geophysics, 2025)

The overlooked shadow killer: Elizabethkingia anophelis as a potent pathogen in American bullfrogs (Aquarana catesbeiana) - Chun Liu; Han Lin; Jie Ma; Yebing Yu; Ruinan Wang; Xinyi Tang; Jingyang Sun; Zhendong Qin; Biao Jiang; Wei Li; Youlu Su; Li Lin (Aquaculture, 2025)

Expanding the pH range of Fenton-like reactions for pollutant degradation: The impact of acidic microenvironments - Shi-Lin Xu; Wei Wang; Yi Song; Rui Tang; Zhen-Hu Hu; Xiao Zhou; Han-Qing Yu (Water Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Bromelain hydrolysis and CaCl2 coordination promote the fibrillation of quinoa protein at pH 7 - Lixiao Fu; Xiao Feng; Chaosheng Wu; Jianfeng Wei; Lin Chen; Xi Yu; Qin Liu; Xiaozhi Tang (Food Hydrocolloids, 2025)

Efficiently radiation-induced degradation and extraction of Polygonatum sibiricum polysaccharides and its excellent ROS scavenging properties - Dong-Xu Tang; Shi-Zhong Zhou; Zhi-Jun Wang; Yang-Lin Zhang; Kun Liu; Jin-Yu Yang; Xiao-Jie Yang; Yue-Sheng Li; Xia Zhang (Chemical Engineering Journal, 2025)

Characteristics of Tylvalosin Tartrate Enteric Amorphous Pellets Prepared by Liquid Layering - Haoran Wang; Lin Han; Han Zeng; Mengyao Yu; Tian Yin; Yu Zhang; Haibing He; Jingxin Gou; Xing Tang (Pharmaceutical Research, 2025)

Sesquiterpenoids from the whole plants of Elephantopus mollis with cytotoxicity activities - Qiang Lin; Jing-Yi Du; Si-Yu Yang; Zhao-Chun Zhan; Qing Tang; Hui Sun; Jin-Lin Tan; Hai-Yue Zhao; Yao-Lan Li; Yu-Bo Zhang; Guo-Cai Wang (Natural Product Research, 2025)

Integrated transcriptomic and proteomic analysis unravels the response mechanisms of Saccharina japonica to heat stress - Zhongyuan Lin; Xuelian Liu; Jinbin Lin; Feng Lin; Yijuan Han; Huibin Xu; Hongmei Lin; Weiqi Tang; Yu Qin; Yanbing Zhu; Hui Ni; Jianjun Lu; et al. (Aquaculture, 2025)

Prospects of advanced oxidation processes for high-salinity coking wastewater treatment: A strategy to support sustainable management - Qili Peng; Jiangfang Yu; Ya Pang; Lifei Deng; Jing Tang; Jiajia Wang; Nile Wu; Lin Tang (Resources, Conservation and Recycling, 2025)

The activation of Parageobacillus toebii in hyperthermophilic composting was depended on the bioavailability of raw materials - Shuqun Zhang; Tao Fu; Jiahuan Tang; Dandan Liu; Xincheng Zheng; Huayuan Shangguan; Hao Lin; Zhen Yu; Raymond Jianxiong Zeng (Journal of Environmental Management, 2025)

Comparative analyses of bacterial contamination and microbiome of broiler carcasses in wet market and industrial processing environments - Yuanyuan Zhou; Nan-lin Wang; Jin-qi Cen; Jia-tong Han; Yu-xuan Tang; Zi-qi Xu; Hang Zeng; Kurt Houf; Zhongjia Yu (International Journal of Food Microbiology, 2025)

Fates of bioactive compounds and antioxidant activities of red pitaya pulp upon in vitro gastrointestinal digestion - Xian Lin; Xiangyu Li; Ying Huang; Jing Wen; Yuanshan Yu; Daobang Tang; Baojun Xu; Yujuan Xu (Food Research International, 2025)

Echelon extraction of valuable components from salt lake brine substrate - Xiangting Tang; Jun Chen; Ye Zhang; Jianguo Yu; Sen Lin (Desalination, 2025)

Determinants of soundscape quality of communal open space in Hong Kong - Minqi LIN; Chi Kwan CHAU; Shiu Keung TANG; Wai Kit CHUNG; Ho Man YU (Building and Environment, 2025)

Quantifying the effects of the microphysical hygroscopic restructuring of soot on ensemble optical properties and satellite aerosol optical depth retrievals - Kuo-En Chang; Tang-Huang Lin; Ta-Chih Hsiao; Yi-Ling Chang; Tzu-Chi Lin; Chih-Yu Chan; Charles C.-K. Chou (Science of The Total Environment, 2024)

Environmental contamination and risks of organic UV filters: Source, discharge, analytical methods and implications for ecological and human health - Yue-hong Sun; Heng-Yu Wu; Feng-Qi Xie; Jia-Ru Ma; Qin-Lin Tang; Yan-Fen Chen; Hao Li; You-Sheng Liu; Guang-Guo Ying (Science of The Total Environment, 2024)

Nanoplastics indirectly compromise lettuce growth in hydroponic systems via microbial extracellular vesicles derived from Curvibacter fontanus - Bao-Hong Lee; Yi-Ching Lin; Yu-Juan Zheng; Tang-Long Shen; Ting-Yu Cheng; Chih-Chia Huang; Wei-Hsuan Hsu (Journal of Hazardous Materials, 2024)

Combining fermentation broth with spent water recycling for microalgae cultivation: Nutrient reutilization, biodiesel production and techno-economic simulation - Ruoyu Chu; Haolun An; Lefei Cai; Yu Chen; Guangming Zeng; Jie Yuan; Lin Tang (Journal of Cleaner Production, 2024)

Emerging antibiotic and heavy metal resistance in spore-forming bacteria from pig manure, manure slurry and fertilized soil - Min Yan; Wen Wang; Lei Jin; Guoyou Deng; Xinfeng Han; Xiumei Yu; Junni Tang; Xiangan Han; Menggen Ma; Lin Ji; Ke Zhao; Likou Zou (Journal of Environmental Management, 2024)

High-performance COFs composite nanofiltration membrane fabricated by organobase catalyst - Lin Yu; Jia-Yue Dai; Zhen-Liang Xu; Yin-Xin Fang; Rui Jia; Yong-Jian Tang (Desalination, 2024)

Bio-inspired sustainable electrospun quantum nanostructures for high quality factor enabled face masks and self-powered intelligent theranostics - Loganathan Veeramuthu; Ren-Jie Weng; Wei-Hung Chiang; Archana Pandiyan; Fu-Jie Liu; Fang-Cheng Liang; G. Ranjith Kumar; Hua-Yi Hsu; Yu-Ci Chen; Wen-Yinn Lin; Yao-Chun Tang; Wan-Rong Lin; et al. (Chemical Engineering Journal, 2024)

Enhanced mass scattering efficiencies of background dust aerosols over East Asia following the passage of dust plumes - Chenguang Tang; Yingjing Lin; Pengfei Tian; Jinsen Shi; Tao Deng; Xuejiao Deng; Yu Zou; Lei Zhang (Atmospheric Environment, 2024)

Effects of soil microplastic heterogeneity on plant growth vary with species and microplastic types - Xiao-Mei Zhang; Wei-Long Li; Wei Xue; Michael Opoku Adomako; Min Tang; Lin-Xuan He; Fei-Hai Yu (Science of The Total Environment, 2024)

Synergistic management of nitrogen contamination in overflow wastewater and algal proliferation in lake receiving wastewater based on electrochemical oxidation process - Ya-Ning Wang; Ding Li; Lin Liu; Jia-Fang Xie; Zhi-Tang Lyu; Quan-Bao Zhao; Yu-Ming Zheng (Process Safety and Environmental Protection, 2024)

Mirids secrete a TOPLESS targeting protein to enhance JA-mediated defense and gossypol accumulation for antagonizing cotton bollworms on cotton plants - Yu-Pei Mu; Dian-Yang Chen; Yu-Jie Liu; Ming-Yu Zhu; Xian Zhang; Yin Tang; Jia-Ling Lin; Mu-Yang Wang; Xiao-Xia Shangguan; Xiao-Ya Chen; Chengshu Wang; Ying-Bo Mao (Molecular Plant, 2024)

Tracing potentially toxic elements in button mushroom cultivation and environmental implications: Insights via stable lead (Pb) isotope analysis - Xun Liu; Junjie Yu; Xueping Lu; Manli Yang; Yazhou Liu; Hui Sun; Ying Ni; Guo Lin; Chuansheng Wu; Jun Tang (Journal of Cleaner Production, 2024)

Intrauterine exposure to long-chain perfluorocarboxylic acids (PFCAs) were associated with reduced primary bile acids in three-year-old children: Findings from a prospective birth cohort study - Yu-Ting Guo; Jin-bo Huang; Jing-chuan Xue; Shuang-Jian Qin; Dan Cai; Qi-Zhen Wu; Chu Chu; Cui-lan Tang; Yan-qi Xie; Li-Zi Lin; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Pollution, 2024)

Synergistic effects of metallic IrCo for promoted nitrate reduction in industrial-relevant wastewater level - Yu Tang; Pan Ran; Linjun Zhong; Haohong Liao; Qing Tong; Weixin Zou; Lin Dong (Chemical Engineering Journal, 2024)

Oncogenic miRNAs dependent photothermal-immunotherapy enhanced by on-demand manipulation of immunosuppressive microenvironment using engineered gold nanoparticles for effective treatment of primary and metastatic tumor - Li Chen; Yu Hu; Wenyun Mu; Tao Liu; Wenjun Tang; Lin Weng; Yanmin Zhang; Xin Chen (Chemical Engineering Journal, 2024)

Input panel for handwriting detection based on triboelectric nanogenerator - Zhigang Peng; Wandi Chen; Jianpu Lin; Haonan Wang; Heng Tang; Yu Zhang; Tailiang Guo; Xiongtu Zhou; Chaoxing Wu; Yongai Zhang (Chemical Engineering Journal, 2024)

Development of Ce-doped NH2-UiO-66(Zr) photocatalysts for efficient CO2 reduction in an aqueous system - Chao Yu; Xianjin Zhang; Chenxu Song; Yanna Wang; Jing Lin; Zhonglu Guo; Yujie Zhang; Zhenya Liu; Chunsheng Li; Yan Sun; Chengchun Tang; Yang Huang (Chemical Engineering Journal, 2024)

Ensuring Clinical Excellence: The Mindray SAL9000 Biochemical Immunoassay System - Zhenzhen Zou; Honghui Tang; Erya Xiao; Yu Zhou; Xuebei Yin; Zhen Hu; Yang Cai; Qingzhen Han; Lin Wang (Cell Biochemistry and Biophysics, 2024)

White matter microstructure damage measured by automated fiber quantification correlates with pain symptoms in lung cancer patients - Li Ran; Jiang Liu; Xiaosong Lan; Xiaoyu Zhou; Yong Tan; Jing Zhang; Yu Tang; Lin Tang; Jiuquan Zhang; Daihong Liu (Brain Imaging and Behavior, 2024)

Nrf2 affects DNA damage repair and cell apoptosis through regulating HR and the intrinsic Caspase-dependent apoptosis pathway in TK6 cells exposed to hydroquinone - Lin Chen; Pu Guo; Lu Zhai; Lingxue Yu; Delong Zhu; Xiaoyi Hu; Zhuanzhuan Li; Yuting Chen; Qian Sun; Lei Sun; Hao Luo; Huanwen Tang (Toxicology in Vitro, 2024)

Decreased nitrogen deposition in Beijing over the recent decade and its implications - Ruotong Si; Ziyin Yu; Xin Ma; Zhang Wen; Ting Luo; Wen Xu; Lei Liu; Aohan Tang; Kai Wang; Lin Zhang; Andreas Schweiger; Keith Goulding; et al. (Science of The Total Environment, 2024)

Response of N, P, and metal ions in deep soil layers to long-term cultivation of rubber and rubber-based agroforestry systems - Chang-An Liu; Yu Nie; Jia-Lin Zhang; Jian-Wei Tang; Xin Rao; Kadambot H.M. Siddique (Science of The Total Environment, 2024)

In vivo detection of endogenous toxic phenolic compounds of intestine - Wen-Yu Jin; Jia-Xin Guo; Rongkang Tang; Jielin Wang; Huan Zhao; Meng Zhang; Lin-Zuo Teng; Philippe J. Sansonetti; Yi-Zhou Gao (Journal of Hazardous Materials, 2024)

Complete chromium removal via photocatalytic reduction and adsorption using bimetallic UiO-66(Zr/Al) - Chao Yu; Chenxu Song; Xianjin Zhang; Yanna Wang; Jing Lin; Yang Huang; Zhonglu Guo; Chunsheng Li; Yujie Zhang; Zhenya Liu; Chengchun Tang; Yan Sun (Journal of Environmental Chemical Engineering, 2024)

Two-Level regulation photocatalytic activity of Bi2WO6/COFs with ligand engineering and piezoelectric field for Highly-Efficient degradation of antibiotics - Yujun Ju; Hailong Lin; Chen Chen; Ruien Hou; Zhe Wang; Tinglong Hao; Min Xu; Yu Tang; Fengjuan Chen (Chemical Engineering Journal, 2024)

Silicon promotes biomass accumulation in Phragmites australis under waterlogged conditions in coastal wetland - Yuntao Wu; Xiaodong Zhang; Jiayang Lin; Xia Wang; Shaobo Sun; Qian Hao; Lele Wu; Jingyun Zhou; Shaopan Xia; Xiangbing Ran; Yidong Wang; Jiahuan Tang; et al. (Plant and Soil, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Expression of a novel hydrolase MhpC in Brevibacillus parabrevis BCP-09 and its characteristics for degrading synthetic pyrethroids - Yingyue Zhang; Dan Xiang; Jie Tang; Chuanning Peng; Siqi Chen; Siqi Huang; Qi Wen; Lin Liu; Wenliang Xiang; Qing Zhang; Ting Cai; Xuan Yu (Pesticide Biochemistry and Physiology, 2024)

MaHOS15 negatively regulates plant immune defense induced by banana fusarium wilt via salicylic acid pathway - Xingchen Jia; Kelin Chen; Yinglong Chen; Yi Tang; Hang Rong; Ping Lin; Yuhao Zhou; Chuqiao Wang; Mingyuan Wang; Jianfu Liu; Qizhi Wang; Hailing Yu (Physiological and Molecular Plant Pathology, 2024)

Boronate-modified electro-spun Fe doped carbon nanofibrous membrane for selective dye adsorption, catalytic degradation, and bacterial inhibition in treatment of water - De-yu Tang; Ling-ling Yan; Luo-lin Deng; Xing-han Wang; Ya-li Xiang; Qing-li Li; Juan Lin; Qing-han Zhou (Chemical Engineering Journal, 2024)

Amplification-free and label-free rapid detection of Staphylococcus aureus using solution-gated graphene transistor-based DNA biosensor with hybridization enhancement by interface engineering - Jiayuan Zheng; Jinhua Li; Tianci Lin; Zhanpeng Ren; Fucheng Wang; Zhonghao Shi; Haiyang Yu; Wei Jiang; Wei Tang (Chemical Engineering Journal, 2024)

Interaction of pepper numbing substances with myofibrillar proteins and numbness perception under thermal conditions: A structural mechanism analysis - Shuaiqian Wang; Yu Chen; Yan Lu; Diandian Jiang; Hongbin Lin; Zhenju Jiang; Jie Tang; Wei Dong; Jie Zhao (Food Chemistry, 2024)

Three species of rape responded to cadmium and melatonin alleviating Cd-toxicity in species-specific strategy - Xiao-long Qin; Yu-qing Zhao; De-jun Zhang; Ke-yu Wang; Wen-hui Chen; Zi-Zhong Tang; Yang-er Chen; Shu Yuan; Lin Ye; Ming Yuan (Environmental Pollution, 2024)

Valuable components recovery from wastewater and brine using electrocoagulation-based coupled process: A systematic review - Ye Zhang; Xiangting Tang; Jiayi Zhang; Yi Zhang; Ruoning Yu; Wenshuo Wang; Sen Lin; Jianguo Yu (Desalination, 2024)

Lateral holding behaviour of torpedo piles in spatially variable soil: Development of a probabilistic design approach - Jiang Tao Yi; Shi Jie Xu; Wu Hao Liu; Lin Ding; Zhen Wang; Hong Yu Tang; Xiao Bin Li (Computers and Geotechnics, 2024)

Unveiling the comprehensive performance and safety advancements in PVC films through environmentally friendly PMgLaCe-LDH incorporation - Yongchun Li; Lijuan Qiao; Yu Tang; Zhi Jia; Xiang Guan; Zhaocai Wang; Shuo Xu; Weilu Yang; Yunfei Ma; Yuting Qiao; Bingxin Liu; Li Gao; et al. (Chemical Engineering Journal, 2024)

Converting kitchen waste into value-added fertilizer using thermophilic semi-continuous composting-biofiltration two-stage process with minimized NH3 emission - Xiu-Lin Chu; Xiang-Yu Peng; Zhao-Yong Sun; Cai-Yun Xie; Yue-Qin Tang (Bioresource Technology, 2024)

Positive feedback between the negative phase of interannual component of the Pacific Decadal Oscillation and La Niña - Hong-Shuo Tang; Yu Zhang; Yu Kosaka; Jun-Chao Yang; Qi Shu; Yi Liu; Xiaopei Lin (Climate Dynamics, 2024)

Two new di-tert-butyl-type compounds from a saline-lake derived Streptomyces sp. XZB42 - Ya-Lin Yu; Shuang Chen; Jie-Bin Fang; Xiao-Ming Chen; Xin-Yi Tang; Jin-Hui Wang (Natural Product Research, 2024)

In-situ interfacial polymerization of polyamide TFN membranes by adding a diamino-silane coupling agent: Toward enhanced desalination performance - Huanhuan Wu; Qian Zhang; Bing Xu; Xin Liu; Yakai Lin; Nan Jiang; Hong Yao; Yuanhui Tang; Lin Wang; Lixin Yu; Zhenzhong Yang; Xiaolin Wang (Desalination, 2024)

Impact of metformin on neocortical development during pregnancy: Involvement of ERK and p35/CDK5 pathways - Muhammet Oner; Mei-Chih Chen; Pang-Ting Cheng; Yu-Hsuan Li; Yu-Chiao Cheng; Ayse Celik; Shiuan-Woei Soong; Li-Wen Hsu; Din-You Lin; G.M. Shazzad Hossain Prince; Trayee Dhar; Hsu-Chen Cheng; et al. (Chemosphere, 2024)

High-resolution and real-time wastewater viral surveillance by Nanopore sequencing - Xiaoqing Xu; Yu Deng; Jiahui Ding; Qinling Tang; Yunqi Lin; Xiawan Zheng; Tong Zhang (Water Research, 2024)

Biochar with enhanced performance prepared based on “graphite-structure regulation” conjecture designed to effectively control water pollution - Bolun Zhang; Yiping Jin; Jiacheng Lin; Ziyu Guo; Guang Chen; Yingjie Su; Xiaoxiao Yu; Shanshan Tang; Siji Chen; Jian Li (Science of The Total Environment, 2024)

Establishing theoretical landscapes of identifying electrocatalysts for urea synthesis via dispersed dual-metals anchored on Ti2CO2 MXene - Jinyou Zhong; Dongyue Gao; Zhe Liu; Yadong Yu; Chao Yu; Yi Fang; Jing Lin; Chengchun Tang; Zhonglu Guo (Fuel, 2024)

Mxenes as inorganic fillers for the construction of poly(aryl piperidinium) anion exchange membranes with microphase separation structures to enhance ionic conductivity - Xiuzhu Zhang; Zongxue Yu; Junlei Tang; Jiaqiang Huang; Xunwang Tang; Bing Lin; Shuangshuang Xia (Fuel, 2024)

Enhanced copper removal by magnesium modified biochar derived from Alternanthera philoxeroides - Yingping Zhou; Xiaoyu Wang; Yu Yang; Lijuan Jiang; Xiaolin Wang; Yuqiong Tang; Lin Xiao (Environmental Research, 2024)

A compound enzyme as an additive to a continuous anaerobic dynamic membrane bioreactor for enhanced lignocellulose removal from codigestion: Performance, membrane characteristics and microorganisms - Bao-Shan Xing; Xiang-Lin Chang; Yi Zhang; Sifan Cao; Xi-Fang Tang; Yong-Chen Han; Yu-You Li; Xiaochang C. Wang; Rong Chen (Bioresource Technology, 2024)

Update of Air Quality Health Index (AQHI) and harmonization of health protection and climate mitigation - Kimberly Tasha Jiayi Tang; Changqing Lin; Zhe Wang; Sik Wing Pang; Tze-Wai Wong; Ignatius Tak Sun Yu; Wallace Wai Yip Fung; Md Shakhaoat Hossain; Alexis K.H. Lau (Atmospheric Environment, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

Invasive Spartina alterniflora alters sediment organic carbon mineralization dynamics in a coastal wetland of Southeastern China - Yongcan Jiang; Dong Yang; Jiafang Huang; Yu Wen; Hong Tang; Jianming Xu; Xianbiao Lin; Dongyao Sun; Dengzhou Gao (Frontiers in Marine Science, 2024)
Invasive Spartina alterniflora has significant impacts on sediment carbon pool and turnover in the tidal wetlands of estuaries and coasts. Yet, how this exotic S. alterniflora affects sediment organic carbon mineralization dynamics remains poorly understood. In this study, sediment geochemical properties, organic carbon fractions, and mineralization dynamics were examined in a native Cyperus malaccensis habitat and three invasive S. alterniflora habitats (6-, 10-, and 14-year-old) in summer and winter. We found that invasive S. alterniflora generally increased sediment total organic carbon and their labile fraction contents. The organic carbon mineralization rates and cumulative carbon mineralization amounts were significantly influenced by invasive S. alterniflora , and their values increased with this exotic plant invasion chronosequences. The mineralization rates and cumulative mineralization amounts were also characterized by higher values in surface sediment (0 – 10 cm depth) compared to subsurface sediment (10 – 20 cm depth) and by seasonal variations with higher values in summer than in winter. The sediment organic carbon labile fractions, rather than total organic carbon, were the most important factor affecting carbon mineralization dynamics. The cumulative carbon mineralization amounts exhibited an excellent fit to the first-order kinetic equation ( R 2 ≥ 0.93). The changes in modeled kinetic parameters (potential carbon mineralization amounts ( C 0 ) and carbon mineralization rate constant ( k )) among these four habitats were similar to carbon mineralization rates, implying invasive S. alterniflora promoted the availabilities of organic compounds for microbial respiration metabolism. Overall, our findings highlighted the importance of S. alterniflora invasion in accelerating organic carbon decomposition and carbon dioxide release potential, although it also increases carbon accumulation.

Scene-aware data augmentation for ship detection in SAR images - Yu Tang; Shigang Wang; Jian Wei; Yan Zhao; Jiehua Lin; Jiaqi Yu; Dongliang Li (International Journal of Remote Sensing, 2024)

New sight in arginine-improved flesh quality: Role of MRFs, cyclins, and WNT signaling in grass carp (Ctenopharyngodon idellus) - Yu-Long Ma; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Hong-Mei Ren; Rui-Nan Zhang; Shu-Wei Li; Ling Tang; Lin Feng (Aquaculture, 2024)

Corrigendum to “Arsenic exposure and pulmonary function decline: Potential mediating role of TRAIL in chronic obstructive pulmonary disease patients” [J. Trace Elem. Med. Biol. 83 (2024) 127415] - Ying Liu; Feng-Min Zhu; Juan Xu; You-Peng Deng; Jing Sun; Qi-Yuan He; Zhen-Yu Cheng; Min-Min Tang; Jin Yang; Lin Fu; Hui Zhao (Journal of Trace Elements in Medicine and Biology, 2024)

Arsenic exposure and pulmonary function decline: Potential mediating role of TRAIL in chronic obstructive pulmonary disease patients - Ying Liu; Feng-Min Zhu; Juan Xu; You-Peng Deng; Jing Sun; Qi-Yuan He; Zhen-Yu Cheng; Min-Min Tang; Jin Yang; Lin Fu; Hui Zhao (Journal of Trace Elements in Medicine and Biology, 2024)

Spatial distribution characteristics of carbazole and polyhalogenated carbazoles in water column and sediments in the open Western Pacific Ocean - Songtao Hu; Lijia Jiang; Lingbo Jiang; Leiming Tang; Anura Upasanta Kumara Wickrama Arachchige; Hao Yu; Zhaochao Deng; Longyu Li; Chunsheng Wang; Dongsheng Zhang; Chunlei Chen; Shiquan Lin; et al. (Journal of Hazardous Materials, 2024)

Investigation into the potential mechanism of Bacillus amyloliquefaciens in the fermentation of broad bean paste by metabolomics and transcriptomics - Hongbin Lin; Shiqi Liao; Zesu Zhou; Ziting Yan; Jianhua Zhao; Yue Xiang; Min Xu; Jie Zhao; Ping Liu; Wengwu Ding; Yu Rao; Jie Tang (Food Research International, 2024)

LncRNA NR_030777 promotes mitophagy by targeting CDK1-related mitochondrial fission and ATG12 to attenuate paraquat-induced Parkinson's disease - Nengzhou Chen; Hong Hu; Jianping Tang; Fuli Zheng; Zhenkun Guo; Xinpei Lin; Michael Aschner; Wenya Shao; Guangxia Yu; Ping Cai; Wei-Chun Chou; Siying Wu; et al. (Environmental Pollution, 2024)

Electrochemical oxidation processes based on renewable energy towards carbon neutrality: Oxidation fundamentals, catalysts, challenges and prospects - Yan Yan; Bing Lin; Liehui Zhang; Yingying Wang; Hailong Zhang; Hongpeng Zheng; Taigang Zhou; Yingqing Zhan; Zongxue Yu; Yun Kuang; Junlei Tang (Chemical Engineering Journal, 2024)

A new substrate equalization method for optimizing the influent conditions and fluid flow patterns of a multifed upflow anaerobic sludge blanket reactor with mature anammox granules - Bao-Shan Xing; Xi-Fang Tang; Ling-Hu Li; Yu-Lin Fu; Jia-Yi Liu; Ya-Ge Wang; Xin-Xin Sun; Yu-You Li; Rong Chen; Ren-Cun Jin (Bioresource Technology, 2024)

Differentiation of closely-related species within Acinetobacter baumannii-calcoaceticus complex via Raman spectroscopy: a comparative machine learning analysis - Xue-Song Xiong; Lin-Fei Yao; Yan-Fei Luo; Quan Yuan; Yu-Ting Si; Jie Chen; Xin-Ru Wen; Jia-Wei Tang; Su-Ling Liu; Liang Wang (World Journal of Microbiology and Biotechnology, 2024)

Catalytic hydrodeoxygenation of 5-hydroxymethylfurfural to 2,5-dimethylfuran over Pd-Co bimetallic catalysts supported on MoCx - Yu Chen; Haoquan Guo; Junye Yang; Kaiyang Xu; Xinyu Lu; Yue Yang; Hongqiao Lin; Lizhi Wu; Li Tan; Guohui Yang; Noritatsu Tsubaki; Xiaoli Gu; et al. (Fuel, 2024)

Impact of occupational noise exposure on the hearing level in hospital staffs: a longitudinal study - Tang-Chuan Wang; You-Cheng Yu; Alan Hsu; Jia-Yi Lin; Yung-An Tsou; Chiu-Shong Liu; Kai-Jen Chuang; Wen-Chi Pan; Chin-An Yang; Sung-Lin Hu; Chien-Yi Ho; Tzu-Liang Chen; et al. (Environmental Science and Pollution Research, 2024)

Comparison and development of scanning electron microscope techniques for delicate plant tissues - Jinhong Yuan; Lin Yang; Panpan Yu; Na Tang; Le Liu; Wenke Wang; Pei Wang; Qingxiang Yang; Siyi Guo; Junhua Li (Plant Science, 2024)

The paradigm for exceptional iodine capture by nonporous amorphous electron-deficient cyclophanes - Baoqi Wu; Zhi-Wei Li; Feng Lin; Rongzhi Tang; Wanqing Zhang; Hongwei Liu; Gangfeng Ouyang; Yu Tan (Journal of Hazardous Materials, 2024)

A versatile CuCo@PDA nanozyme-based aptamer-mediated lateral flow assay for highly sensitive, on-site and dual-readout detection of Aflatoxin B1 - Xu Zhu; Jing Tang; Xilian Ouyang; Yibo Liao; Haopeng Feng; Jiangfang Yu; Li Chen; Yating Lu; Yuyang Yi; Lin Tang (Journal of Hazardous Materials, 2024)

Reduction of antigenicity and emulsibility improvement of ovalbumin by dielectric-barrier discharge plasma treatment induced structure modification - Pan-Pan Tang; Lin-Lin Zhang; Yu-Xin Xiong; Dan-Dan Jiang; Xiu-Bin Liu; Jun-Hu Cheng; Rana Muhammad Aadil; Zhi-Wei Liu (Innovative Food Science & Emerging Technologies, 2024)

Characterization of key flavor substances and their microbial sources in traditional sour bamboo shoots - Hui Tang; Jin-Kui Ma; Lin Chen; Li-Wen Jiang; Lin-Zhi Kang; Ying-Yu Guo; Ge-Yang Men; Dan-Xia Nie; Rui-Min Zhong (Food Chemistry, 2024)

Directly capturing native fatty acid synthase from cancer cells by affinity-based probe for precise inhibitor discovery - Yuanyuan Lin; Huaqiu Lu; Jinhao Yu; Xuan Chen; Ningbo Chen; Huamin Zhang; Lu Ye; Yimin Chen; Weiyang Tang; Guizhong Xin; Jian-Liang Zhou (Chemical Engineering Journal, 2024)

Experimental study on strength characteristics and constitutive behavior of frozen chloride silty clay - Yu Tang; Ping Yang; Lin Li; Zhiliang Zhou (Cold Regions Science and Technology, 2024)

Identification of the domestication gene GmCYP82C4 underlying the major quantitative trait locus for the seed weight in soybean - Yang Li; Wenqian Zhao; Jiajun Tang; Xiuli Yue; Jinbao Gu; Biyao Zhao; Cong Li; Yanhang Chen; Jianbo Yuan; Yan Lin; Yan Li; Fanjiang Kong; et al. (Theoretical and Applied Genetics, 2024)

Prognostic significance and immune escape implication of tumor-infiltrating neutrophil plasticity in human head and neck squamous cell carcinoma - Xiaoke Zhu; Yu Heng; Duo Zhang; Di Tang; Jian Zhou; Hanqing Lin; Jingyu Ma; Xuping Ding; Lei Tao; Liming Lu (Human Cell, 2024)

Mechanism of deltamethrin biodegradation by Brevibacillus parabrevis BCP-09 with proteomic methods. - Yingyue Zhang; Jie Tang; Su Wang; Xuerui Zhou; Chuanning Peng; Hu Zhou; Dan Wang; Haoran Lin; Wenliang Xiang; Qing Zhang; Ting Cai; Xuan Yu (Chemosphere, 2024)

Comparison of four pre-oxidants coupled powdered activated carbon adsorption for odor compounds and algae removal: Kinetics, process optimization, and formation of disinfection byproducts - Heng-Xuan Zhao; Shuang Zhang; Tian-Yang Zhang; Yi-Ping Zhu; Ren-Jie Pan; Meng-Yuan Xu; Zheng-Xiong Zheng; Chen-Yan Hu; Yu-Lin Tang; Bin Xu (Science of The Total Environment, 2024)

Clinical landscape and prognosis of patients with gastric cancer liver metastases: A nation-wide multicenter cohort study in China (RECORD study) - Yunhe Gao; Hongqing Xi; Liang Shang; Zhaoqing Tang; Bo Wei; Zhi Qiao; Yun Tang; Xinxin Wang; Jing Zhou; Xuefei Wang; Changming Huang; Jun Lu; et al. (Science Bulletin, 2024)

Process-based evaluation of carbon emissions from the on-site construction of prefabricated steel structures: A case study of a multistory data center in China - Zujian Huang; Hao Zhou; Hao Tang; Deyin Zhang; Yang Zhao; Juan Yu; Minjie Luo; Yicheng Wang; Borong Lin (Journal of Cleaner Production, 2024)

Vegetation−fire feedbacks increase subtropical wildfire risk in scrubland and reduce it in forests - P. Wei; B. Lamont; T. He; W. Xue; P.C. Wang; W. Song; R. Zhang; A.B. Keyhani; S. Zhao; W. Lu; F. Dong; R. Gao; et al. (Journal of Environmental Management, 2024)

The underappreciated role of fugitive VOCs in ozone formation and health risk assessment emitted from seven typical industries in China - Zhiling Liang; Yunjiang Yu; Bingbing Sun; Qian Yao; Xihua Lin; Yongsheng Wang; Jianping Zhang; Yingzi Li; Xuefeng Wang; Zhengzheng Tang; Shexia Ma (Journal of Environmental Sciences, 2024)

3D network of zinc powder woven into fibre filaments for dendrite-free zinc battery anodes - Lin Sha; Bin-Bin Sui; Peng-Fei Wang; Zhe Gong; Yu-Hang Zhang; Yu-Han Wu; Li-Na Zhao; Jun-Jie Tang; Fa-Nian Shi (Chemical Engineering Journal, 2024)

GW4064 inhibits migration and invasion through cathepsin B and MMP2 downregulation in human bladder cancer - Chien-Chang Kao; Chien-Rui Lai; Yi-Hsuan Lin; Tzu-Min Chen; Yu-Ling Tsai; Wen-Chiuan Tsai; Tze-Yun Ong; Hisao-Hsien Wang; Sheng-Tang Wu; Ying Chen (Chemico-Biological Interactions, 2024)

Environmental selenium and human longevity: An ecogeochemical perspective - Bo Li; Xu Liu; Tao Yu; Kun Lin; Xudong Ma; Cheng Li; Zhongfang Yang; Qifeng Tang; Guodong Zheng; Jianxun Qin; Ying Wang (Chemosphere, 2024)

Attenuated AKT signaling by miR-146a-5p interferes with chicken granulosa cell proliferation, lipid deposition and progesterone biosynthesis - Yuan Tang; Zhongzhen Lin; Li Liu; Lingqian Yin; Donghao Zhang; Chunlin Yu; Chaowu Yang; Yanrong Gong; Yan Wang; Yiping Liu (Theriogenology, 2024)

Microplastics elicit an immune-agitative state in coral - Chuan-Ho Tang; Ching-Yu Lin; Hsing-Hui Li; Fu-Wen Kuo (Science of The Total Environment, 2024)

Reciprocal transplant experiment reveals multiple factors influencing changes in coral microbial communities across climate zones - Ya-Fan Chan; Yu-Hsiang Chen; Sheng-Ping Yu; Hsing-Ju Chen; Yoko Nozawa; Sen-Lin Tang (Science of The Total Environment, 2024)

Can public opinion persuade the government to strengthen the use of environmental regulation policy tools? Evidence from policy texts - Song Chai; Mengxian Wei; Lin Tang; Xintian Bi; Yawen Yu; Jin Yang; Zhu Jie (Journal of Cleaner Production, 2024)

Reduced contribution of microbial necromass carbon to soil organic carbon following tunnel construction in the eastern Qinghai-Tibet Plateau - Yuzhuo Chen; Jincheng Xiang; Xiaodong Wang; Yang Xiao; Benjamin Laffitte; Shurui He; Du Yu; Guo Chen; Lin Li; Xiangjun Pei; Xiaolu Tang (Journal of Cleaner Production, 2024)

Modulating the microenvironment of catalytic interface with functional groups for efficient photocatalytic degradation of persistent organic pollutants - Yujun Ju; Ze Wang; Hailong Lin; Ruien Hou; Hua Li; Zhe Wang; Ruitong Zhi; Xiaoquan Lu; Yu Tang; Fengjuan Chen (Chemical Engineering Journal, 2024)

Effects of Aegilops longissima chromosome 1Sl on wheat bread-making quality in two types of translocation lines - Yuliang Qiu; Zhiyang Han; Ningtao Liu; Mei Yu; Shuangxi Zhang; Haiqiang Chen; Huali Tang; Zhiyong Zhao; Ke Wang; Zhishan Lin; Fangpu Han; Xingguo Ye (Theoretical and Applied Genetics, 2024)

Individual preferences, jobs, or amenities? Understanding the destination choices of highly and less-skilled migrants in urban China - Yu Wang; Sainan Lin; Shuangshuang Tang (Applied Geography, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Precipitation consistently promotes, but temperature oppositely drives carbon fluxes in temperate and alpine grasslands in China - Zhaogang Liu; Zhi Chen; Meng Yang; Tianxiang Hao; Guirui Yu; Xianjin Zhu; Weikang Zhang; Lexin Ma; Xiaojun Dou; Yong Lin; Wenxing Luo; Lang Han; et al. (Agricultural and Forest Meteorology, 2024)

Scenarios of temporal environmental alterations and phytoplankton diversity in a changing bay in the East China Sea - Yu Wang; Weibo Wang; Yaqin Huang; Lin Chang; Xiaoming Tang; Xuebao He; Hui Lin (Frontiers in Marine Science, 2023)
In the context of global change, the stressors of warming and eutrophication have significant ecological implications in coastal waters. In order to examine the diversity of phytoplankton and its relationship with water quality, we conducted a survey of phytoplankton community compositions and their correlation with environmental changes over four seasons in a eutrophic bay located in the East China Sea. Through a systematic analysis, we identified diatoms and dinoflagellates as the primary dominant groups, with the species Skeletonema costatum , Skeletonema marinoi , Biddulphia sinensis , Thalassiosira eccentrica , Leptocylindrus danicus , Coscinodiscus oculus-iridis , Coscinodiscus jonesianus , and Chaetoceros knipowitschi as the most abundant species in all seasons. Significant seasonal alterations were observed in both environmental settings and phytoplankton species richness, dominance, and abundance. The phytoplankton community varied in its response to diverse aquatic environments and was principally affected by temperature, silicic acid concentrations, and suspended solids. Elevated temperatures were found to promote an increase in phytoplankton abundance. However, no clear evidence of diatom and dinoflagellate succession in relation to N:P ratio was observed across seasons. Water quality analysis illustrated that the majority of the study area exhibited a mid-eutrophic with severe organic pollution. The abundance of phytoplankton was significantly influenced by eutrophication and organic pollution. The accelerated warming process related to coastal nuclear power plants and nutrient regime alterations significantly affect the temporal shift of the phytoplankton community. These findings contribute valuable insights into the effects of eutrophic environments on the structure of phytoplankton communities in coastal aquatic systems.

Isalo scorpion Cytotoxic peptide (IsCT) improved the physical barrier of the intestine on on-growing grass carp (Ctenopharyngodon idella) - Chong Zhang; Qi-Yu Hu; Lin Feng; Pei Wu; Yang Liu; Sheng-Yao Kuang; Ling Tang; Jiang Li; Xiao-Qiu Zhou; Wei-Dan Jiang (Aquaculture, 2023)

Mixed chlorine/chloramines in disinfected water and drinking water distribution systems (DWDSs): A critical review - Renjie Pan; Tian-Yang Zhang; Huan He; Zheng-Xiong Zheng; Zheng-Yu Dong; Heng-Xuan Zhao; Meng-Yuan Xu; Zhen-Ning Luo; Chen-Yan Hu; Yu-Lin Tang; Mohamed Gamal El-Din; Bin Xu (Water Research, 2023)

pH-Responsive graphene oxide/poly (methacrylic acid) hybrid nanofiltration membrane performance for water treatment - Li-yue Sun; De-hao Yu; Zhao-ge Juan; Yao Wang; Yan-xin Wang; Matt J. Kipper; Lin-jun Huang; Jian-guo Tang (Journal of Environmental Chemical Engineering, 2023)

Quality changes and path analysis of color degradation of Dendrobium officinale flower juice during storage - Xuewen Dong; Jie Tang; Xiaoting Qin; Shenglan Tian; Huasi Lin; Qiang Yu; Xiaobo Hu; Mingyong Xie (Food Bioscience, 2023)

MiR-7-5p targeted Rb regulating cell cycle is involved in hydroquinone-induced malignant progression in human lymphoblastoid TK6 cells - Lu Zhai; Yuting Gao; Zheming Cui; Lin Chen; Lingxue Yu; Pu Guo; Delong Zhu; Huanwen Tang; Xin Liu; Hao Luo (Food and Chemical Toxicology, 2023)

Binary-1D/2D nanomaterial-functionalization toward strong, stretchable, and anti-freezing electrically conductive organohydrogels for self-powered operation monitoring of robotic hand - Jie Zhou; Bo Tang; Dong Li; Cheng-Wei You; Yu-Yao Zhao; Lin-Yue Li; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2023)

Suppress moisture sensitivity of Ni-rich cathode materials by bioinspired self-assembly hydrophobic layer - Yingde Huang; Pei-Yao Li; Han-Xin Wei; Yu-Hong Luo; Lin-Bo Tang; He-Zhang Chen; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2023)

CDK6 is a novel predictive and prognosis biomarker correlated with immune infiltrates in multiple human neoplasms, including small cell lung carcinoma - Guo-Sheng Li; Zhi-Guang Huang; Dong-Ming Li; Yu-Lu Tang; Jin-Hua Zheng; Lin Yang; Yue Feng; Jun-Xi Peng; Jing-Xiao Li; Yu-Xing Tang; Neng-Yong Zeng; Mei-Hua Jin; et al. (Functional & Integrative Genomics, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Miticidal activity of Photorhabdus luminescens for controlling two spider mites, Tetranychus urticae and Tetranychus kanzawai, in Carica papaya - Tzay-Tien Hsieh; Ju-Chun Chang; Chienyan Hsieh; Jui-Tang Tseng; Show-Jow Lin; Cheng-Ju Yang; Feng-Chia Hsieh; Yu-Shin Nai (BioControl, 2023)

Investigation of the Artificial Saliva and Saline Droplet Size Measurement Accuracy for COVID-19 Infection Control - Thomas Y. Wu; Yi-Hung Liu; Fang-hsin Lin; Yue Liu; Junjie Liu; Jinsang Jung; Wesley Zongrong Yu; Qinde Liu; Richard Y. C. Shin; Tang Lin Teo (Aerosol Science and Engineering, 2023)

Soil selenium enrichment in the Loess Plateau of China: Geogenic evidence, spatial distribution, and it's influence factors - Xuezhen Li; Qingye Hou; Yiren Duan; Yongchun Li; Kun Lin; Bo Li; Weikang Sheng; Yongliang Wang; Rilige Su; Zhoulei Gu; Tao Yu; Qifeng Tang; et al. (Chemosphere, 2023)

Contribution of free hydroxyl radical to the formation of micro(nano)plastics and release of additives during polyethylene degradation in water - Yu Tang; Kaiqing Fan; Indika Herath; Williamson Gustave; Chuxia Lin; Junhao Qin; Rongliang Qiu (Environmental Pollution, 2023)

Advances and promotion strategies of membrane-based methods for extracting lithium from brine - Yu-ning Zhang; De-hao Yu; Chen-yu Jia; Li-yue Sun; Ang Tong; Yao Wang; Yan-xin Wang; Lin-jun Huang; Jian-guo Tang (Desalination, 2023)

Fabrication of diamond/copper composite thin plate based on a single-layer close packed diamond particles network for heat dissipation - Jia-wan Peng; Feng-lin Zhang; Yu-mei Zhou; Ling-kang Xiong; Yao-jie Huang; Hong-qun Tang (Chemical Engineering Journal, 2023)

Large-diameter trees buffer monsoonal changes to tree biomass over two decades - Chen-Chia Ku; Jianwu Tang; Wei-Chun Chao; Kuo-Jung Chao; Guo-Zhang Michael Song; Huan-Yu Lin; James A. Lutz (Plant Ecology, 2023)

Induction of Anxiety-Like Phenotypes by Knockdown of Cannabinoid Type-1 Receptors in the Amygdala of Marmosets - Lin Zhu; Di Zheng; Rui Li; Chen-Jie Shen; Ruolan Cai; Chenfei Lyu; Binliang Tang; Hao Sun; Xiaohui Wang; Yu Ding; Bin Xu; Guoqiang Jia; et al. (Neuroscience Bulletin, 2023)

Ammonia assimilation is key for the preservation of nitrogen during industrial-scale composting of chicken manure - Lin Zhu; Caihong Huang; Wei Li; Weixia Wu; Zhurui Tang; Yu Tian; Beidou Xi (Waste Management, 2023)

Boron nitride aerogels incorporated with metal nanoparticles: Multifunctional platforms for iodine capture and detection - Gen Li; Jianli Liang; Jing Lin; Hongyu Li; Yan Liu; Guoyang Xu; Chao Yu; Zhonglu Guo; Chengchun Tang; Yang Huang (Journal of Hazardous Materials, 2023)

Association of greenness surrounding school with aggression among adolescents: A multi-site study in China - Yi Zhang; Yanqi Li; Xinyi Xie; Xiaoyi Lin; Mengxin Huang; Huihang Fu; Weiju Zhou; John S. Ji; Yizhen Yu; Jie Tang (Environmental Research, 2023)

Unlocking ventilation flexibility of large airport terminals through an optimal CO2-based demand-controlled ventilation strategy - Hao Tang; Juan Yu; Yang Geng; Zhe Wang; Xue Liu; Zujian Huang; Borong Lin (Building and Environment, 2023)

A pan-coronavirus peptide inhibitor prevents SARS-CoV-2 infection in mice by intranasal delivery - Lili Wu; Anqi Zheng; Yangming Tang; Yan Chai; Jiantao Chen; Lin Cheng; Yu Hu; Jing Qu; Wenwen Lei; William Jun Liu; Guizhen Wu; Shaogui Zeng; et al. (Science China Life Sciences, 2023)

A highly sensitive self-powered sensing method designed on DNA circuit strategy and MoS2 hollow nanorods for detection of thalassemia - Jinyue Shi; Danyao Tang; Yu Lin; Yeyu Wu; Hu Luo; Jun Yan; Ke-Jing Huang; Xuecai Tan (Analytica Chimica Acta, 2023)

Neurobehavioral disorders induced by environmental zinc in female zebrafish (Danio rerio): Insights from brain and intestine transcriptional and metabolic signatures - Fan Yu; Zhi-Shuai Hou; Hong-Rui Luo; Hong-Xia Li; Xue-Fan Cui; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Qin-Feng Gao; Jun Xiao; Pao Xu (Chemosphere, 2023)

Conjugated polymers S-scheme homojunction with large internal electric field and matching interface for efficient visible light photocatalytic degradation of ciprofloxacin - Mingjuan Zhang; Lin Tang; Yuan Zhu; Yi Zhang; Junli Liu; Jiajia Wang; Chengyang Feng; Lu Qiao; Yu Chen (Journal of Cleaner Production, 2023)

Spatio-temporal distribution of organochlorine pesticides in agricultural soils of southeast China during 2014-2019 - Wei Zuo; Qin Lin; Xinju Liu; Lu Lv; Chunrong Zhang; Shenggan Wu; Xi Cheng; Yijun Yu; Tao Tang (Environmental Research, 2023)

Honey bee foraging ability suppressed by imidacloprid can be ameliorated by adding adenosine - Yu-Chun Lin; Yun-Heng Lu; Cheng-Kang Tang; En-Cheng Yang; Yueh-Lung Wu (Environmental Pollution, 2023)

Decorating {0 0 1} TiO2 nanosheets on hydrophobic NaY zeolite: An efficient deactivation-resistant photocatalyst for gaseous toluene removal - Juntao Tang; Mengying Fu; Yidan Mao; Shuyi Yang; Wei Lin; Yan Yu; Shuang Song (Chemical Engineering Journal, 2023)

An anaerobic dynamic membrane bioreactor (AnDMBR) system enhanced the biogas conversion efficiency and stability of mesophilic codigestion with waste activated sludge and food waste - Bao-Shan Xing; Yi Zhang; Rui-Qi Zhang; Jing Ma; Xiang-Lin Chang; Xi-Fang Tang; Yu-You Li; Xiaochang C. Wang; Rong Chen (Chemical Engineering Journal, 2023)

Dihydromyricetin attenuates cisplatin-induced acute kidney injury by reducing oxidative stress, inflammation and ferroptosis - Zheming Xu; Minjing Zhang; Wenwen Wang; Suhan Zhou; Minghua Yu; Xingyu Qiu; Shan Jiang; Xiaohua Wang; Chun Tang; Shuijie Li; Chih-Hong Wang; Runzhi Zhu; et al. (Toxicology and Applied Pharmacology, 2023)

Changes in soil Cd contents and microbial communities following Cd-containing straw return - Haojie Xu; Yu Huang; Xinquan Xiong; Hang Zhu; Jiahui Lin; Jiachun Shi; Caixian Tang; Jianming Xu (Environmental Pollution, 2023)

Rational design of surface reconstruction with pinning effect to relieving bulk fatigue for high energy single-crystal Ni-rich cathodes - Ying-de Huang; Han-Xin Wei; Pei-Yao Li; Lin-Bo Tang; Yu-Hong Luo; Xin-Ming Fan; Cheng Yan; Jing Mao; Ke-Hua Dai; He-Zhang Chen; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2023)

Culturing reef-building corals on a laboratory dish: a simple experimental platform for stony corals - Shinya Shikina; Tzu-Chieh Lin; Yu-Ling Chu; Yin-Chu Cheng; Yu-En Chang; Naohisa Wada; Sen-Lin Tang; Yoshiyuki Iizuka; Yi-Ling Chiu (Frontiers in Marine Science, 2023)
Development and maintenance of coral reef ecosystems rely on daily micro-biological activities of healthy corals. Although a comprehensive understanding of coral biological properties, as well as factors negatively affecting coral growth, are essential to conserve existing corals, the current lack of a tractable culture and experimental platform has delayed acquisition of such knowledge. Here we show a highly versatile culture system, “coral-on-a-laboratory dish” (CLD), allowing long-term culturing of various corals in plastic/glass Petri dishes with maintenance of their biological properties. Under optimized conditions, coral microcolonies (~5 mm x 5 mm fragments) of Pocillopora damicornis were cultured for several months in dishes with high survivorship and characteristic growth. These microcolonies maintained their biological properties, such as reproduction, skeleton formation, coral-algal symbiosis, ingestion, and digestion. Thus far, CLD has been used to maintain at least 4 other coral species from 4 other families, including the Acroporidae, the Pocilloporidae, the Poritidae, and the Merulinidae for more than 2 months with 100% survivorship. CLD is applicable to a variety of biophysiological studies, including coral-algal symbiosis and impact assessment of marine pollutants, e.g., a sunscreen substance, oxybenzone, and an organic biocide, Irgarol 1051, at cellular-level resolution. The CLD platform, which allows easy and inexpensive coral maintenance in a laboratory incubator, represents a technological breakthrough that will greatly advance coral studies.

Estimating arsenic biotransfer factors from feed to chicken: a viable approach to animal feed risk assessment - Ching-Chi Hung; Hsin-Tang Lin; Ching-Yi Chen; Kuan-Yi Chen; Tsung-Yu Lee; Chow-Feng Chiang (Food Additives & Contaminants: Part A, 2023)

An electronic sense-based machine learning model to predict formulas and processes for vegetable-fruit beverages - Hai-Bin Ren; Bao-Long Feng; Hong-Yue Wang; Jing-Jian Zhang; Xiao-Sen Bai; Fei Gao; Yan Yang; Qi Zhang; Ye-Hui Wang; Li-Li Wang; Ya-Ting Rong; Yu-Lin Sun; et al. (Computers and Electronics in Agriculture, 2023)

Four cases of reported adverse effects from black boletoi, Anthracoporus nigropurpureus (Boletaceae) mushroom ingestion - Jing Ma; Jing Xia; Hai-Jiao Li; Lin-Jie Su; Rou Xue; Shuai Jiang; Tai-Jie Yu; Yi Liu; Li-Ping Tang (Toxicon, 2023)

Long-term in-situ starvation and reactivation of co-digestion with food waste and corn straw in a continuous AnDMBR: Performance, sludge characteristics, and microorganism community - Bao-Shan Xing; Xiang-Lin Chang; Sifan Cao; Dong Wu; Yi Zhang; Xi-Fang Tang; Yu-You Li; Xiaochang C. Wang; Rong Chen (Science of The Total Environment, 2023)

The deficiency of N6-methyladenosine demethylase ALKBH5 enhances the neurodegenerative damage induced by cobalt - Chunyan Zheng; Guangxia Yu; Qianqian Su; Lingyan Wu; Jianping Tang; Xinpei Lin; Yao Chen; Zhenkun Guo; Fuli Zheng; Hong Zheng; Liqiong Lin; Ying Tang; et al. (Science of The Total Environment, 2023)

Insight into mixed chlorine/chloramines conversion and associated water quality variability in drinking water distribution systems - Renjie Pan; Tian-Yang Zhang; Zheng-Xiong Zheng; Jian Ai; Tao Ye; Heng-Xuan Zhao; Chen-Yan Hu; Yu-Lin Tang; Jing-Jing Fan; Bing Geng; Bin Xu (Science of The Total Environment, 2023)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

Cobalt induces neurodegeneration through FTO-triggered autophagy impairment by targeting TSC1 in an m6A-YTHDF2-dependent manner - Jianping Tang; Fuli Zheng; Xu Liu; Yanjun Li; Zhenkun Guo; Xinpei Lin; Jinfu Zhou; Yu Zhang; Guangxia Yu; Hong Hu; Wenya Shao; Siying Wu; et al. (Journal of Hazardous Materials, 2023)

Variation in microbiological heterogeneity in Chinese strong-flavor Baijiu fermentation for four representative varieties of sorghum - Mao-Ke Liu; Yu-Ming Tang; Cheng-Yuan Liu; Xin-Hui Tian; Ji-Wei Zhang; Xiao-Li Fan; Kai-Feng Jiang; Xian-Lin Ni; Xin-Yu Zhang (International Journal of Food Microbiology, 2023)

Cadmium exposure caused cardiotoxicity in common carps (Cyprinus carpio L.): miR-9-5p, oxidative stress, energetic impairment, mitochondrial division/fusion imbalance, inflammation, and autophagy - Yuhao Liu; Xu Lin; Zhiyu Hao; Meijin Yu; You Tang; Xiaohua Teng; Wei Sun; Lu Kang (Fish & Shellfish Immunology, 2023)

Relating critical and limiting fluxes to metastable and long-term stable fluxes in colloidal membrane filtration through collision-attachment theory - Junxia Liu; Wei Fu; Xuri Yu; Haiyan Yang; Dongsheng Zhao; Zhihong Wang; Lin Wang; Xianhui Li; Chuyang Y. Tang (Water Research, 2023)

Hydrogen sulfide antagonizes formaldehyde-induced ferroptosis via preventing ferritinophagy by upregulation of GDF11 in HT22 cells - Yu-Hui Tang; Lei Wu; Hong-Lin Huang; Pan-Pan Zhang; Wei Zou; Xiao-Qing Tang; Yi-Yun Tang (Toxicology, 2023)

Residential greenness, air pollution and incident neurodegenerative disease: A cohort study in China - Zhanghang Zhu; Zongming Yang; Luhua Yu; Lisha Xu; Yonghao Wu; Xinhan Zhang; Peng Shen; Hongbo Lin; Liming Shui; Mengling Tang; Mingjuan Jin; Jianbing Wang; et al. (Science of The Total Environment, 2023)

Sex-specific effect of perfluoroalkyl substances exposure on liver and thyroid function biomarkers: A mixture approach - Ze Yang; Ruifang Liu; Hongbo Liu; Jiemin Wei; Xiaohui Lin; Mingyue Zhang; Yu Chen; Jingyun Zhang; Meiqing Sun; Zhe Feng; Jian Liu; Xiangyang Liu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Superior sorption capacity and one-step reduction of Au(III) by a novel chitosan-based electrospun fiber mat: A cheap and simple technique - Chuanhao Yan; Xuefeng Yu; Wenyi Jia; Jinglei He; Jing Hu; Meng Zhang; Jianlong Wang; Lin Tang; Junfeng Liu; Xilong Wang (Chemical Engineering Journal, 2023)

Spatiotemporal variations and impact factors of nutrients in the Sanya Bay, northern South China Sea - Xinxing Geng; Chuanliang Wu; Ziwei Yang; Junying Zhu; Kai Tang; Jiamin Lin; Yaxing Liu; Yufang Zhang; Mingxun An; Weibin Zhao; Yang Yu (Environmental Science and Pollution Research, 2023)

Synergistic effect of intercalation and EDLC electrosorption of 2D/3D interconnected architectures to boost capacitive deionization for water desalination via MoSe2/mesoporous carbon hollow spheres - Jiaxin Du; Wenle Xing; Jiaqi Yu; Jing Feng; Lin Tang; Wangwang Tang (Water Research, 2023)

Polybrominated diphenyl ethers and bromophenols in paired serum, hair, and urine samples of e-waste dismantlers: Insights into hair as an indicator of endogenous exposure - Meiqing Lin; Shengtao Ma; Jian Tang; Yingxin Yu; Guiying Li; Ruifang Fan; Guoxia Zhang; Bixian Mai; Taicheng An (Science of The Total Environment, 2023)

Identification and genomic characterization of Ralstonia pseudosolanacearum strains isolated from pepino melon in China - Shanwen Ding; Lin Yu; Guobing Lan; Yafei Tang; Zhenggang Li; Zifu He; Xiaoman She (Physiological and Molecular Plant Pathology, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Failure mechanism of a large-scale composite deposits caused by the water level increases - Xin Zhang; Guo-xiang Tu; Qi-feng Luo; Hao Tang; Yu-lin Zhang; An-run Li (Journal of Mountain Science, 2023)

Nano-Fe3O4 coated on carbon monolith for anode enhancement in microbial fuel cells - Yini Chen; Fan Zhao; Yu Pu; Xiangyu Lin; Haoran Yin; Xinhua Tang (Journal of Environmental Chemical Engineering, 2023)

Valorizing kitchen waste to produce value-added fertilizer by thermophilic semi-continuous composting followed by static stacking: Performance and bacterial community succession analysis - Xiang-Yu Peng; Shi-Peng Wang; Xiu-Lin Chu; Zhao-Yong Sun; Zi-Yuan Xia; Cai-Yun Xie; Min Gou; Yue-Qin Tang (Bioresource Technology, 2023)

Spinal P2X4 Receptors Involved in Visceral Hypersensitivity of Neonatal Maternal Separation Rats - Ying Tang; Li Chen; Bin Liu; Pei Sun; Zhong Chen; Yang Huang; Chen Ai-qin; Yu Chen; Chun Lin (Purinergic Signalling, 2023)

Correction to: Protective Effects of Chinese Herbal Medicine Rhizoma drynariae in Rats After Traumatic Brain Injury and Identification of Active Compound - Wenzhu Wang; Haigang Li; Jintao Yu; Michael Hong; Jing Zhou; Lin Zhu; Yang Wang; Min Luo; Zian Xia; Zeng-Jin Yang; Tao Tang; Ping Ren; et al. (Molecular Neurobiology, 2023)

Effects of habitat usage on hypoxia avoidance behavior and exposure in reef-dependent marine coastal species - Haolin Yu; Guangjie Fang; Kenneth A. Rose; Jiazheng Lin; Jie Feng; Haiyan Wang; Qingxian Cao; Yanli Tang; Tao Zhang (Frontiers in Marine Science, 2023)
Reef habitat in coastal ecosystems is increasingly being augmented with artificial reefs (ARs) and is simultaneously experiencing increasing hypoxia due to eutrophication and climate change. Relatively little is known about the effects of hypoxia on organisms that use complex habitat arrangements and how the presence of highly preferred AR habitat can affect the exposure of organisms to low dissolved oxygen (DO). We performed two laboratory experiments that used video recording of behavioral movement to explore 1) habitat usage and staying duration of individuals continuously exposed to 3, 5, and 7 mg/L dissolved oxygen (DO) in a complex of multiple preferred and avoided habitat types, and 2) the impact of ARs on exposure to different DO concentrations under a series of two-way replicated choice experiments with or without AR placement on the low-oxygen side. Six common reef-dependent species found in the northeastern sea areas of China were used (i.e., rockfish Sebastes schlegelii and Hexagrammos otakii , filefish Thamnaconus modestus , flatfish Pseudopleuronectes yokohamae , sea cucumber Stichopus japonicus , and crab Charybdis japonica ). Results showed that lower DO levels decreased the usage of preferred habitats of the sea cucumber and the habitat-generalist filefish but increased the habitat affinity to preferred habitat types for the two habitat-specific rockfishes. Low DO had no effect on the crab’s habitat usage. In the choice experiment, all three fish species avoided 1 mg/L, and the rockfish S. schlegelii continued to avoid the lower DO when given choices involving pairs of 3, 5, and 7 mg/L, while H. otakii and the flatfish showed less avoidance. The availability of ARs affected exposure to low DO for the habitat-preferring rockfishes but was not significant for the flatfish. This study provides information for assessing the ecological effects and potential for adaptation through behavioral movement for key reef-dependent species under the increasing overlap of ARs and hypoxia anticipated in the future.

Effect of Iodine Nutrition Status on Thyroid Function and Pregnancy Outcomes - Hongying Zha; Lin Yu; Yi Tang; Lu Sun; Qingxin Yuan (Biological Trace Element Research, 2023)

Sequential combination of pre-chlorination and powdered activated carbon adsorption on iodine removal and I-THMs control in drinking water - Renjie Pan; Yi-Li Lin; Tian-Yang Zhang; Xiu-Li Wei; Zheng-Yu Dong; Chen-Yan Hu; Yu-Lin Tang; Bin Xu (Chemosphere, 2023)

Enrofloxacin exposure induces anxiety-like behavioral responses in zebrafish by affecting the microbiota-gut-brain axis - Dandan Tian; Wei Shi; Yihan Yu; Weishang Zhou; Yu Tang; Weixia Zhang; Lin Huang; Yu Han; Guangxu Liu (Science of The Total Environment, 2023)

Association of walkability and fine particulate matter with chronic obstructive pulmonary disease: A cohort study in China - Yonghao Wu; Peng Shen; Zongming Yang; Luhua Yu; Zhanghang Zhu; Tiezheng Li; Lisha Xu; Dan Luo; Xuecheng Yao; Xinhan Zhang; Lin Meng; Hongbo Lin; et al. (Science of The Total Environment, 2023)

Handwipes as indicators to assess organophosphate flame retardants exposure and thyroid hormone effects in e-waste dismantlers - Jian Tang; Shengtao Ma; Xin Hu; Meiqing Lin; Guiying Li; Yingxin Yu; Taicheng An (Journal of Hazardous Materials, 2023)

A high-efficient anisotropic continuum model for the optimization of heat transfer and chemical reaction in a packed-bed water gas shift reactor - Bo Jiang; Haonan Wang; Kewei Yu; Jing Ma; Wang Si-ma; Yuming Gao; Lin Li; Xinwei Zhang; Huiru Cui; Dawei Tang (Fuel, 2023)

Horizontal transfer of intracellular and extracellular ARGs in sludge compost under sulfamethoxazole stress - Zhurui Tang; Caihong Huang; Wei Li; Wenxuan Li; Wenbing Tan; Beidou Xi; Yu Tian; Lin Zhu (Chemical Engineering Journal, 2023)

In-situ construction and repair of high catalytic activity interface on corrosion-resistant high-entropy amorphous alloy electrode for hydrogen production in high-temperature dilute sulfuric acid electrolysis - Yangzheng Li; Junlei Tang; Hailong Zhang; Yingying Wang; Bing Lin; Jichao Qiao; Hongpeng Zheng; Zongxue Yu; Yiding Liu; Taigang Zhou; Xianzhang Lei (Chemical Engineering Journal, 2023)

Somatostatin-Positive Neurons in the Rostral Zona Incerta Modulate Innate Fear-Induced Defensive Response in Mice - Shan Lin; Meng-Yue Zhu; Meng-Yu Tang; Mi Wang; Xiao-Dan Yu; Yi Zhu; Shi-Ze Xie; Dan Yang; Jiadong Chen; Xiao-Ming Li (Neuroscience Bulletin, 2023)
Defensive behaviors induced by innate fear or Pavlovian fear conditioning are crucial for animals to avoid threats and ensure survival. The zona incerta (ZI) has been demonstrated to play important roles in fear learning and fear memory, as well as modulating auditory-induced innate defensive behavior. However, whether the neuronal subtypes in the ZI and specific circuits can mediate the innate fear response is largely unknown. Here, we found that somatostatin (SST)-positive neurons in the rostral ZI of mice were activated by a visual innate fear stimulus. Optogenetic inhibition of SST-positive neurons in the rostral ZI resulted in reduced flight responses to an overhead looming stimulus. Optogenetic activation of SST-positive neurons in the rostral ZI induced fear-like defensive behavior including increased immobility and bradycardia. In addition, we demonstrated that manipulation of the GABAergic projections from SST-positive neurons in the rostral ZI to the downstream nucleus reuniens (Re) mediated fear-like defensive behavior. Retrograde trans-synaptic tracing also revealed looming stimulus-activated neurons in the superior colliculus (SC) that projected to the Re-projecting SST-positive neurons in the rostral ZI (SC-ZIr SST -Re pathway). Together, our study elucidates the function of SST-positive neurons in the rostral ZI and the SC-ZIr SST -Re tri-synaptic circuit in mediating the innate fear response.

The detection of major clades and new species of Mallocybe (Inocybaceae, Agaricales) from China with elongate cheilocystidia - Jian-Hua Hu; Wen-Jie Yu; Lun-Sha Deng; Yu-Guang Fan; Tolgor Bau; Li-Ping Tang; Wen-Fei Lin; Chun-Ying Deng (Mycological Progress, 2023)

Low 15d-PGJ2 status is associated with oxidative stress in chronic obstructive pulmonary disease patients - Shi-Xue Ma; Guo-Fang Xie; Pu Fang; Min-Min Tang; You-Peng Deng; Yu-Jin Lu; Wei Cao; Lin Fu (Inflammation Research, 2023)

Gastropod chemoreception behaviors—Mechanisms underlying the perception and location of targets and implications for shellfish fishery development in aquatic environments - Zheng-Lin Yu; Mei-Jie Yang; Hao Song; Tao Zhang; Xiu-Tang Yuan (Frontiers in Marine Science, 2023)
Chemoreception is one of the most important senses and it plays a key role in the survival and adaptation of animals to their environments. Many gastropods, such as Rapana venosa and Neptunea cumingii , have emerged as economically important shellfish. Meanwhile, invasive gastropods have destroyed commercial shellfisheries in many countries. Given the importance of chemoreception in the behavior of aquatic gastropods, the mechanism of their chemical perception has recently garnered attention. To provide a foundation for understanding the chemoreception of aquatic gastropods, we reviewed recent studies and summarized the chemoreception behaviors and mechanisms that gastropods use to perceive and locate targets in aquatic environments, along with relevant molecular and genetic insights. We highlight several of the implications of these studies for chemoreception-related research and shellfish fishery development. This review should aid in the rational development and utilization of gastropod resources as well as in controlling the populations of invasive species.

The construction of high efficient visible-light-driven 3D porous g-C3N4/Fe3O4 photocatalyst: A new photo-induced bacterial inactivation material enhanced by cascade photo-Fenton reaction - Ze-Yu Liu; Wen-Qian Huang; Chuan-Qing Huang; Zhao-Zhen Liu; Xiao-Yue Tang; Wei-Chang Chen; Zheng-Zheng Tang; Yu-Xing Huang; Shuo-Chun Zheng; Lin Lin; Changzhu Li; Yong Ye (Chemosphere, 2023)

Association between exposure to perfluoroalkyl substances and uric acid in Chinese adults - Ze Yang; Kun Men; Jiaxin Guo; Ruifang Liu; Hongbo Liu; Jiemin Wei; Jingyun Zhang; Liangpo Liu; Xiaohui Lin; Mingyue Zhang; Yong Liu; Yu Chen; et al. (Chemosphere, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Hemin protects UVB-induced skin damage through inhibiting keratinocytes apoptosis and reducing neutrophil infiltration - Fang Bai; Chen Fan; Xi Lin; Hao-Yu Wang; Bing Wu; Chun-Lan Feng; Rong Zhou; Yan-Wei Wu; Wei Tang (Journal of Photochemistry and Photobiology B: Biology, 2023)

Insight into the Co2+/Co3+ sites for the selective reduction of furfural to furfuryl alcohol - Jiahong Chen; Wenlong Jia; Xin Yu; Yong Sun; Jiaren Zhang; Shuliang Yang; Xing Tang; Lincai Peng; Xianhai Zeng; Lu Lin (Fuel, 2023)

Breast adipose metabolites mediates the association of tetrabromobisphenol a with breast cancer: A case-control study in Chinese population - Ai Zhang; Rui Wang; Qianfeng Liu; Zhengjun Yang; Xiaohui Lin; Jing Pang; Xiaoyu Li; Dan Wang; Jiayu He; Jianping Li; Mingyue Zhang; Yue Yu; et al. (Environmental Pollution, 2023)

Nonoxidative propane dehydrogenation by isolated Co2+ in BEA zeolite: Dealumination-determined key steps of propane C H activation and propylene desorption - Sheng Wei; Hua Dai; Jiangping Long; Hongqiao Lin; Junkun Gu; Xupeng Zong; Dan Yang; Yu Tang; Yanhui Yang; Yihu Dai (Chemical Engineering Journal, 2023)

13.2% EQE near-infrared TADF OLED with emission peak at 761 nm - Jing-Wen Tai; Yukun Tang; Kai Zhang; Chen-Zong Yang; Ze-Hui Pan; Yu-Ching Lin; Yu-Wei Shih; Chia-Hsun Chen; Tien-Lung Chiu; Jiun-Haw Lee; Chuan-Kui Wang; Chung-Chih Wu; et al. (Chemical Engineering Journal, 2023)

Hydroxychloroquine repairs burn damage through the Wnt/β-catenin pathway - Sheau-Chung Tang; Chun-Te Lu; Jiunn-Liang Ko; Cheng-Hui Lin; Yu-Ping Hsiao (Chemico-Biological Interactions, 2023)

RNAseq-based transcriptome analysis of lettuce infected by the necrotrophic fungus Sclerotinia Sclerotiorum - Liguang Tang; Bincai Wang; Liping Song; Chuying Yu; Chufa Lin; Changbin Gao; Daohong Jiang; Aihua Wang (European Journal of Plant Pathology, 2023)

Physiological and transcriptome analysis of Mytilus coruscus in response to Prorocentrum lima and microplastics - Xiao-wen Tang; Rong Yu; Mei-hua Fan; Zhi Yang; Zhi Liao; Zong-xin Yang; Chen-ying Xie; Yu-kun Xuan; Jian-xin Wang; Xiao-lin Zhang; Xiao-jun Yan (Frontiers in Marine Science, 2022)
Nowadays, diarrheic shellfish toxicity (DSP) toxin and microplastics (MPs) are commonly found in coastal waters worldwide. Due to their widespread use, their persistence and toxicity, they may induce adverse effects on Mytilus coruscus . However, the underlying toxic mechanisms of DSP and MPs on M. coruscus remain unclear. This study explored the physiological index and transcriptome change of the digestive gland of adult M. coruscus exposed for 3 days to polystyrene (PS) MPs (0.2 mg/L, 90-100 μm) and Prorocentrum lima alone or in combination. The results showed that the CAT activity and MDA content significantly increased, respiration rate and feeding rate significantly decreased. The combination of MPs and P. lima caused more structural damage to the rough surface endoplasmic reticulum and mitochondria in the digestive glands of M. coruscus . The transcriptome analysis showed that 485 and 220 genes were up- and down-regulated, respectively, after exposure to P. lima ; 1,989 up-regulated DEGs and 1,098 down-regulated DEGs were identified after exposure to MP treatment, and 1,004 up-regulated DEGs and 664 down-regulated DEGs were identified after exposure to the combination of P. lima and MPs. The DEGs were mainly enriched in the lysosome, mRNA surveillance pathway, carbon metabolism, the mTOR signaling pathway, the complement and coagulation cascades, and the TNF signaling pathway. The MP, P. lima exposure mainly induced the expression of RNA-binding protein musashi, serine/arginine repetitive matrix protein 1, low affinity immunoglobulin epsilon Fc receptor, toll-like receptor 2, caspase 7, calmodulin, E3 ubiquitin-protein ligase, serine/threonine-protein kinase PRP4, glutathione S-transferase, and heat shock 70 kDa protein. MPs and P. lima poison mainly influence the expression of RNA transport, immune related gene, apoptosis, signal related gene, and antioxidant gene change. The combination of MPs and P. lima has a synergistic toxic effect. This study provides a new insights into its physiological and molecular responses of M. coruscus to MPs and P. lima toxic exposure.

Phycospheric bacterial community structure and function succession during the typical harmful macroalgal blooms - Tongfei Qu; Chengzong Hou; Chen Guan; Xinyu Zhao; Jun Chen; Yi Zhong; Jinhui Xu; Zhihao Lin; Yu Xu; Xuexi Tang; Ying Wang (Frontiers in Marine Science, 2022)
Based on the diversity and importance of phycospheric microorganisms as well as their complex interaction with algae, their ecological correlation with algal bloom events has become a research topic of great interest that remains unclear in the natural dynamic process of harmful macroalgal blooms (HMBs). The world’s largest green tides caused by macroalgae Ulva prolifera have occurred in the Yellow Sea for 16 consecutive years, and seriously affected the coastal ecosystem. Here, we monitored the spatiotemporal dynamics of the phycospheric bacterial community during the U . prolifera green tide bloom. The 73-day continuous field survey covered the whole process of initial invasion until the extinction of the green tide. The phycospheric bacterial community has a higher richness than the control seawater bacteria; in addition, it has more enriched taxa with organic nutrition preference and environmental pressure adaption, such as Bacteroidetes, Firmicutes, and Desulfobacterota. The same differences in populations and functional profiles were observed among the epiphytic bacterial and phycospheric seawater bacterial communities, which may be driven by the spatial heterogeneity of biogenic elements (e.g., organic nutrients and oxygen) among the habitats. Significant succession occurred in both the epiphytic bacterial and phycospheric seawater bacterial communities; their diversity and richness exhibited significant heterogeneity variation patterns, and their community structure became more similar in late phases. Our study revealed that macroalgal phycospheric microbial communities have a highly complex and dynamic composition and variable ecological functions, which indicate that phycospheric microorganisms are closely related to the fate of HMBs and may have the profound effect coastal biogeochemical cycles.

Combined analysis of mRNA and miRNA reveals the banana potassium absorption regulatory network and validation of miRNA160a - Wenliang Chen; Tao Dong; Yinglong Chen; Ping Lin; Chuqiao Wang; Kelin Chen; Yi Tang; Mingyuan Wang; Jianfu Liu; Hailing Yu (Plant Molecular Biology, 2022)

Potential risk from and prevention of phytoplankton outbreaks in blocking the cooling water system in a nuclear power plant on the Southeast China coast - Yu Wang; Xiaoyin Chen; Yingyue Lin; Shuyi Zhang; Lin Chang; Xiaoming Tang; Peng Xiang; Heshan Lin (Frontiers in Marine Science, 2022)
The invasion or aggregation of marine biota in coastal waters has become a common problem, threatening the safety of cooling water systems in the context of environmental and climate changes. However, studies on issues of coastal nuclear power plants from the view of marine ecology have mostly focused on the thermal effluent, entrainment effect on organisms, residual chlorine, radioactivity, etc. There is a lack of information on the safety of cooling water systems in nuclear power plants blocked by marine biota. Based on field and historical datasets, this study screened phytoplankton species that may potentially block the cooling water system of the Fuqing nuclear power plant on the Southeast China coast, identified the phytoplankton risk and a risk calendar, and established a catalog of risk phytoplankton species for the cooling water system. The screening criteria were simultaneously required as follows: (1) particle size of cells or group >2000 μm; (2) phytoplankton bloom or aggregation events occurred in surrounding areas; (3) and species abundance maintained at >0.5×10 5 cells/L in the surrounding area. Nine high-risk species were screened out that can easily form colonies, clusters, and groups, including Thalassiosira diporocyclus , Thalassiosira subtilis , Noctiluca scintillans , Phaeocystis globosa , Pseudo-nitzschia pungens , Pseudo-nitzschia delicatissima , Skeletonema costatum , Skeletonema dohrnii , Paralia sulcata . Due to small cells or the formation of short chains, some dominant phytoplankton species, even those with advantages in abundance and occurrence, had difficulty threatening the reliability of cooling water systems in nuclear power plants. The outbreak of different phytoplankton species varied daily, and the risk of blockage was highest from April to July. The biological characteristics, ecological mechanisms underlying outbreaks of high-risk phytoplankton species are reviewed and discussed, suggesting a high degree of temporal and spatial variability of blockage risk. Finally, main prevention and control measures used against high-risk phytoplankton species are provided to imply new ideas and methods for nuclear power plants. These strategies have very important practical and scientific significance.

A Facile, Label-free and Versatile Fluorescence Sensing Nanoplatform Based on Titanium Carbide Nanosheets for the Detection of Various Targets - Meishuang Liang; Bixia Lin; Zhijiao Tang; Li Zhang; Manli Guo; Yujuan Cao; Yumin Wang; Ying Yu (Journal of Fluorescence, 2022)

Bifunctional Ni@NiO catalyst supported on loofah sponge-derived carbon for electrocatalytic air oxidation of biorefractory pollutant in a coupling system - Min Sun; Xiong-Fei Tao; Sheng-Nan Tang; Jun Yu; Yan Wang; Lin-Feng Zhai (Environmental Science and Pollution Research, 2022)

The Key Role of Magnetic Resonance Imaging in the Detection of Neurodegenerative Diseases-Associated Biomarkers: A Review - Ke-Ru Li; An-Guo Wu; Yong Tang; Xiao-Peng He; Chong-Lin Yu; Jian-Ming Wu; Guang-Qiang Hu; Lu Yu (Molecular Neurobiology, 2022)

Functional analysis of HADH c.99C>G shows that the variant causes the proliferation of pancreatic islets and leu-sensitive hyperinsulinaemia - Wu Long; Yue-Bing Wang; Peng-Fei Qu; Lin Ma; Si-Jie Wei; Yan-Mei Xi; Jin-Liang Du; Xue Tang; Kai Liu; Yu-Hua Li; Pu-Ping Lei (Journal of Genetics, 2022)

The Chinese species of skipper butterflies in the tribe Tagiadini Mabille, 1878 (Lepidoptera: Hesperiidae): insights from phylogeny, hostplants, and biogeography - Li Shen; Jianqing Zhu; Yuxiang Lin; Jie Fang; Yongqiang Wang; Liying Tang; Qinghao Zhao; Mengqi Xiao; Feiyu Duan; Qunxiu Liu; Weidong Yu; Weibin Jiang (Organisms Diversity & Evolution, 2022)

Nanobubbles loaded with carbon quantum dots for ultrasonic fluorescence dual detection - Yankun Zhang; Bingtao Tang; Yu Xin; Qiong Wu; Lan Liu; Yunxia Wang; Kongxi Zhu; Guimei Lin; Hongjuan Wang (Journal of Zhejiang University-SCIENCE B, 2022)

Two new clerodane diterpenoids and a new pyran-2-one derivative with anti-neuroinflammatory activities from Croton crassifolius - Zhi-Peng Ling; Qing Tang; Can-Jie Li; Jin-Lin Tan; Hai-Yue Zhao; Yi-Kun Hao; Zhao-Chun Zhan; Zhong-Nan Wu; Yu-Bo Zhang; Qing Zheng; Guo-Cai Wang (Journal of Natural Medicines, 2022)

Application of the Non-dominated Sorting Genetic Algorithm II in Multi-objective Optimization of Orally Disintegrating Tablet Formulation - Jiaqi Zhang; Yu Yao; Wei Sun; Liling Tang; Xiaodong Li; Huaqing Lin (AAPS PharmSciTech, 2022)

Three new sesquiterpene lactones from the whole plants of Elephantopus scaber - Ding-Chai Lin; Qing Tang; Xue-Fang Zhuo; Wen-Zhi Wang; Can-Jie Li; Guang-Kai Kuang; Zhong-Nan Wu; Yu-Bo Zhang; Guo-Cai Wang; Yao-Lan Li (Natural Product Research, 2022)

Identification of the Largest SCA36 Pedigree in Asia: with Multimodel Neuroimaging Evaluation for the First Time - Yue Xie; Zhao Chen; Zhe Long; Rui-Ting Chen; Yi-Zheng Jiang; Ming-Jie Liu; Lin-Liu Peng; Hui-Rong Peng; Na Wan; Guangdong Zou; Chun-Rong Wang; Yu-Ting Shi; et al. (The Cerebellum, 2022)

Transcriptome Changes Induced by Botrytis cinerea Stress and Weighted Gene Co-expression Network Analysis (WGCNA) in Actinidia chinensis - Zhe-Xin Li; Wen-Lin Zhang; Deng-Wei Jue; Xia Liu; Yu-Song Jiang; Jian-Min Tang (Plant Molecular Biology Reporter, 2022)

A Deep Mesencephalic Nucleus Circuit Regulates Licking Behavior - Di Zheng; Jia-Yu Fu; Meng-Yu Tang; Xiao-Dan Yu; Yi Zhu; Chen-Jie Shen; Chun-Yue Li; Shi-Ze Xie; Shan Lin; Minmin Luo; Xiao-Ming Li (Neuroscience Bulletin, 2022)

Environmental risks and the potential benefits of nanopesticides: a review - Zhenlan Xu; Tao Tang; Qin Lin; Jianzhong Yu; Changpeng Zhang; Xueping Zhao; Melanie Kah; Lingxiangyu Li (Environmental Chemistry Letters, 2022)

Investigation on long-term progressive deformation of engineering slope based on comprehensive monitoring - Shi-shu Zhang; Song-feng Guo; Sheng-wen Qi; Feng-jiao Tang; Jin-shan Hu; Xiao-ping Zhao; Cong-yan Ran; Xin Wang; Yu Zou; Xiao-lin Huang; Bo-wen Zheng; Ning Liang (Journal of Mountain Science, 2022)

Distinct Evolution of the SST Anomalies in the Far Eastern Pacific between the 1997/98 and 2015/16 Extreme El Niños - Shaolei Tang; Jing-Jia Luo; Lin Chen; Yongqiang Yu (Advances in Atmospheric Sciences, 2022)

Pusillimonas faecipullorum sp. nov., isolated from the poultry manure - Shih-Yao Lin; Asif Hameed; Chia-Fang Tsai; Yu-Shan Tang; Chiu-Chung Young (Archives of Microbiology, 2022)

Ocean Currents May Influence the Endolithic Bacterial Composition in Coral Skeletons - Po-Yu Liu; Sung-Yin Yang; Chih-Ying Lu; Naohisa Wada; Stéphane De Palmas; Shu-Shuo Yeh; Hideyuki Yamashiro; Sen-Lin Tang; Shan-Hua Yang (Frontiers in Marine Science, 2022)
Coral endolithic microbes can be an important nutrients support for hosts while under stresses. Previous studies have found that the endolithic microbial composition of a single coral species can be biogeographical diverse. However, the potential environmental factors, such as salinity, temperature, pH, and nutrient, that might influence the composition of the endolithic microbes remain unclear. In this study, we used both amplicon sequence variants (ASV) and a kmer-based taxonomic unit (KTU) to characterize the endolithic bacterial constitution of Isopora spp. located in the western Pacific Ocean—where it is subjected to the Kuroshio Current (in Okinawa, Japan and Green Island, Taiwan)—and the South China Sea (Dongsha Atoll). The endolithic bacterial community compositions showed a significant geographical difference, and we suggest that the ocean current and primary productivity are the most essential environmental factors influencing the bacterial communities in the skeleton of Isopora spp. In addition, our results showed that, technically, compared to ASV, bacterial composition based on KTU avoids extreme data, making it a suitable tool for explaining the associations between microbes and environmental factors.

Genetic Diversity Analysis of Sugarcane (Saccharum spp. hybrids) Among High-Sucrose Clones of GT Series and Commonly Used Parents by Using Microsatellite Markers in Guangxi, China - Hai-Rong Huang; Yi-Jing Gao; Mukesh Kumar Malviya; Krishan K. Verma; Manoj Kumar Solanki; Yu-Xin Huang; Xiang Li; Yuchi Deng; Jing Yan; Shi-Yun Tang; Lun-Wang Wang; Lin Xu (Sugar Tech, 2022)

Heat Shock Procedure Affects Cell Division-Associated Genes in Gynogenetic Manipulation - Fan Yu; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Pao Xu; Huan Zhong (Marine Biotechnology, 2022)

Prevalence, complete genome, and metabolic potentials of a phylogenetically novel cyanobacterial symbiont in the coral‐killing sponge, Terpios hoshinota - Yu‐Hsiang Chen; Hsing‐Ju Chen; Cheng‐Yu Yang; Jia‐Ho Shiu; Daphne Z. Hoh; Pei‐Wen Chiang; Wenhua Savanna Chow; Chaolun Allen Chen; Tin‐Han Shih; Szu‐Hsien Lin; Chi‐Ming Yang; James Davis Reimer; et al. (Environmental Microbiology, 2022)
Summary Terpios hoshinota is an aggressive, space‐competing sponge that kills various stony corals. Outbreaks of this species have led to intense damage to coral reefs in many locations. Here, the first large‐scale 16S rRNA gene survey across three oceans revealed that bacteria related to the taxa Prochloron , Endozoicomonas , SAR116, Ruegeria , and unclassified Proteobacteria were prevalent in T . hoshinota . A Prochloron ‐related bacterium was the most dominant and prevalent cyanobacterium in T . hoshinota . The complete genome of this uncultivated cyanobacterium and pigment analysis demonstrated that it has phycobiliproteins and lacks chlorophyll b , which is inconsistent with the definition of Prochloron . Furthermore, the cyanobacterium was phylogenetically distinct from Prochloron , strongly suggesting that it should be a sister taxon to Prochloron . Therefore, we proposed this symbiotic cyanobacterium as a novel species under the new genus Candidatus Paraprochloron terpiosi. Comparative genomic analyses revealed that ‘Paraprochloron’ and Prochloron exhibit distinct genomic features and DNA replication machinery. We also characterized the metabolic potentials of ‘Paraprochloron terpiosi’ in carbon and nitrogen cycling and propose a model for interactions between it and T. hoshinota . This study builds a foundation for the study of the T . hoshinota microbiome and paves the way for better understanding of ecosystems involving this coral‐killing sponge.

A First Insight Into the Heat-Induced Changes in Proteomic Profiles of the Coral Symbiotic Bacterium Endozoicomonas montiporae - Ya-Fan Chan; Chia-Yu Chen; Chih-Ying Lu; Yung-Chi Tu; Kshitij Tandon; Shinya Shikina; Sen-Lin Tang (Frontiers in Marine Science, 2022)
Endozoicomonas , a core bacterial group in corals, may also be a coral symbiont. Endozoicomonas communities often decrease rapidly in corals under heat stress. However, how the bacteria respond to changes in temperature and coral host during heat stress is unknown. Here, we employed the cultivable, dominant species E. montiporae as a working organism to explore how Endozoicomonas responds to heat stress. We designed two experiments to clarify the extent to which E. montiporae is influenced by temperature and coral host. We detected differentially expressed protein (DEP) profiles in this bacterium at 31 and 33°C compared to 25°C by tandem mass tags-based quantitative proteome analysis. Fifty DEPs, including many heat shock proteins, were detected when the temperature changed. The expression of antioxidant defense proteins and key pyruvate synthase proteins decreased, suggesting that E. montiporae were in a physiology of stress at 33°C. Furthermore, some proteins were differentially expressed because of the heat-stress-treated coral lysate specifically, suggesting that not only heat but also heat-induced host factors can affect the protein expression of the bacterium. This study provides an in-depth analysis of how the molecular mechanisms of Endozoicomonas are affected by heat stress and coral host.

The lining responses for shallow mountain tunnels subjected to frost heaving - Xian-zhang Ling; Yuan Yu; Liang Tang; Lin Geng; Xiao Han (Journal of Mountain Science, 2022)

Natural forests promote phosphorus retention in soil - Zhen Yu; Zhou Guoyi; Lei Liu; Stefano Manzoni; Philippe Ciais; Daniel Goll; Josep Peñuelas; Jordi Sardans; Wantong Wang; Jie Zhu; Lin Li; Junhua Yan; et al. (Global Change Biology, 2022)
Soil phosphorus (P) availability often limits plant productivity. Classical theories suggest that total P content declines at the temporal scale of pedogenesis, and ecosystems develop toward the efficient use of scarce P during succession. However, the trajectory of ecosystem P within shorter time scales of succession remains unclear. We analyzed changes to P pools at the early (I), middle (II), and late (III) stages of growth of plantation forests (PFs) and the successional stages of natural forests (NFs) at 1969 sites in China. We found significantly lower P contents at later growth stages compared to earlier ones in the PF ( p p

MAPK5 and MAPK10 overexpression influences strawberry fruit ripening, antioxidant capacity and resistance to Botrytis cinerea - Yunting Zhang; Yu Long; Yiting Liu; Min Yang; Liangxin Wang; Xiaoyang Liu; Yong Zhang; Qing Chen; Mengyao Li; Yuanxiu Lin; Haoru Tang; Ya Luo (Planta, 2022)

PHD2 attenuates high-glucose-induced blood retinal barrier breakdown in human retinal microvascular endothelial cells by regulating the Hif-1α/VEGF pathway - Jia Li; Xi Lu; Liqing Wei; Dan Ye; Jianqiang Lin; Xiaoyu Tang; Kaixuan Cui; Shanshan Yu; Yue Xu; Xiaoling Liang (Inflammation Research, 2022)

Expression profiling of WRKY transcription factors in Spinach - Yaying Ma; Shuai Chen; Hongying Yu; Ruoyu Li; Zhicong Lin; Mingxing Cai; Min Tang; Xingtan Zhang; Ray Ming (Euphytica, 2021)

A New Instrumental Array in Sichuan, China, to Monitor Vibrations and Perturbations of the Lithosphere, Atmosphere, and Ionosphere - Chieh-Hung Chen; Yang-Yi Sun; Kai Lin; Chen Zhou; Rui Xu; Haiyin Qing; Yongxin Gao; Tao Chen; Fei Wang; Huaizhong Yu; Peng Han; Chi-Chia Tang; et al. (Surveys in Geophysics, 2021)

Meta-analyses of maternal exposure to atmospheric particulate matter and risk of congenital anomalies in offspring - Guangxia Yu; Yao Chen; Jianping Tang; Zhifeng Lin; Fuli Zheng; Chunyan Zheng; Jinfu Zhou; Qianqian Su; Siying Wu; Huangyuan Li (Environmental Science and Pollution Research, 2021)

Production of purple Ma bamboo (Dendrocalamus latiflorus Munro) with enhanced drought and cold stress tolerance by engineering anthocyanin biosynthesis - Mengqi Xiang; WenSha Ding; Chu Wu; Wenjia Wang; Shanwen Ye; Changyang Cai; Xin Hu; Nannan Wang; Weiyuan Bai; Xiaoshan Tang; Caiping Zhu; Xiaomin Yu; et al. (Planta, 2021)

The major photoprotective role of anthocyanins in leaves of Arabidopsis thaliana under long-term high light treatment: antioxidant or light attenuator? - Xiao-Ting Zheng; Zheng-Chao Yu; Jun-Wei Tang; Min-Ling Cai; Yi-Lin Chen; Cheng-Wei Yang; Wah Soon Chow; Chang-Lian Peng (Photosynthesis Research, 2021)

Synthesis and biological evaluation of novel 1,3-diphenylurea quinoxaline derivatives as potent anticancer agents - Gui-Zhen Li; Xi-Lin Ouyang; Zu-Yu Mo; Yao Gu; Xiao-Lin Cao; Li Yang; Hai-Tao Tang; Ying-Ming Pan (Medicinal Chemistry Research, 2021)

Nucleophosmin/B23 promotes endometrial cancer cell escape from macrophage phagocytosis by increasing CD24 expression - Chiao-Yun Lin; Chia-Lung Tsai; Angel Chao; Li-Yu Lee; Wei-Chun Chen; Yun-Hsin Tang; An-Shine Chao; Chyong-Huey Lai (Journal of Molecular Medicine, 2021)

Five matrine-type alkaloids from Sophora tonkinensis - Qing Tang; Ding Luo; Ding-Chai Lin; Wen-Zhi Wang; Can-Jie Li; Xue-Fang Zhuo; Zhong-Nan Wu; Yu-Bo Zhang; Guo-Cai Wang; Yao-Lan Li (Journal of Natural Medicines, 2021)

Complete genome sequence of a previously undescribed monopartite begomovirus and betasatellite infecting Malvastrum coromandelianum in Cambodia - Yafei Tang; Zhenggang Li; Xiaoman She; Lin Yu; Guobing Lan; Lihua Lv; Judith K. Brown; Zifu He (Archives of Virology, 2021)

Application of solid-phase extraction based on magnetic nanoparticle adsorbents for the analysis of selected persistent organic pollutants in environmental water: A review of recent advances - Aiming Wu; Xiaoli Zhao; Junyu Wang; Zhi Tang; Tianhui Zhao; Lin Niu; Wenqiang Yu; Chunyan Yang; Mengyuan Fang; Hongzhou Lv; Shasha Liu; Fengchang Wu (Critical Reviews in Environmental Science and Technology, 2021)

Heterosis-associated genes confer high yield in super hybrid rice - Tianzi Lin; Cong Zhou; Gaoming Chen; Jun Yu; Wei Wu; Yuwei Ge; Xiaolan Liu; Jin Li; Xingzhou Jiang; Weijie Tang; Yunlu Tian; Zhigang Zhao; et al. (Theoretical and Applied Genetics, 2020)
Key message Heterosis QTLs, including qSS7 and qHD8, with dominance effects were identified through GBS and large-scale phenotyping of CSSLs and hybrid F 1 populations in a paddy field. Abstract Heterosis has contributed immensely to agricultural production, but its genetic basis is unclear. We evaluated dominance effects by creating two hybrid populations: a B-homo set with a homozygous background and heterozygous chromosomal segments and a B-heter set with a heterozygous background and homozygous segments. This was achieved by crossing a set of 156 backcrossed-derived chromosome segment substitution lines (CSSLs) with their recurrent parent (9311), the male parent of the first super-high-yield hybrid Liangyoupei9 (LYP9), and with the female parent (PA64s) of the hybrid. The CSSLs were subjected to a genotyping-by-sequencing analysis to develop a genetic map of segments introduced from the PA64s. We evaluated the heterotic effects on eight yield-related traits in the hybrid variety and F 1 populations in large-scale field experiments over 2 years. Using a linkage map consisting of high-density SNPs, we identified heterosis-associated genes in LYP9. Five candidate genes contributed to the high yield of LYP9, with qSS7 and qHD8 repeatedly detected in both B-hybrid populations. The heterozygous segments harboring qSS7 and qHD8 showed dominance effects that contributed to the heterosis of yield components in the hybrid rice variety Liangyoupei9.

A review of the Chinese monotypic genus Melliodendron (Styracaceae), with a new synonym of M. xylocarpum - Xue-Hui Wu; Rui Zhang; Timothy M. A. Utteridge; Yu-Lin Liu; Guang-Yao Yang; Ming Tang (Kew Bulletin, 2020)

Effects of intercropping accumulator plants and applying their straw on the growth and cadmium accumulation of Brassica chinensis L. - Yi Tang; Liming Wang; Yongdong Xie; Xuena Yu; LiJin Lin; Huanxiu Li; Ming’an Liao; Zhihui Wang; Guochao Sun; Dong Liang; Hui Xia; Xun Wang; et al. (Environmental Science and Pollution Research, 2020)

Matriptase and prostasin proteolytic activities are differentially regulated in normal and wounded skin - Shun-Cheng Chang; Chien-Ping Chiang; Chih-Hsin Lai; Po-Wen A. Du; Yu-Sin Hung; Yu-Hsuan Chen; Hui-Yu Yang; Hao-Yu Fang; Shiao-Pieng Lee; Hung-Jen Tang; Jehng-Kang Wang; Michael D. Johnson; et al. (Human Cell, 2020)

FGOALS-g3 Model Datasets for CMIP6 Flux-Anomaly-Forced Model Intercomparison Project - Yaqi Wang; Zipeng Yu; Pengfei Lin; Hailong Liu; Jiangbo Jin; Lijuan Li; Yanli Tang; Li Dong; Kangjun Chen; Yiwen Li; Qian Yang; Mengrong Ding; et al. (Advances in Atmospheric Sciences, 2020)
The Flux-Anomaly-Forced Model Intercomparison Project (FAFMIP) is an endorsed Model Intercomparison Project in phase 6 of the Coupled Model Intercomparison Project (CMIP6). The goal of FAFMIP is to investigate the spread in the atmosphere-ocean general circulation model projections of ocean climate change forced by increased CO 2 , including the uncertainties in the simulations of ocean heat uptake, global mean sea level rise due to ocean thermal expansion and dynamic sea level change due to ocean circulation and density changes. The FAFMIP experiments have already been conducted with the Flexible Global Ocean-Atmosphere-Land System Model, gridpoint version 3.0 (FGOALS-g3). The model datasets have been submitted to the Earth System Grid Federation (ESGF) node. Here, the details of the experiments, the output variables and some baseline results are presented. Compared with the preliminary results of other models, the evolutions of global mean variables can be reproduced well by FGOALS-g3. The simulations of spatial patterns are also consistent with those of other models in most regions except the North Atlantic and the Southern Ocean, indicating large uncertainties in the regional sea level projections of these two regions.

Anthraquinone derivatives from a coral associated fungus Stemphylium lycopersici - Jiao Li; Yu-Bing Zheng; Tibor Kurtán; Ming-Xiang Liu; Hua Tang; Chun-Lin Zhuang; Wen Zhang (Natural Product Research, 2020)

Enhancement of the activity of Cu/TiO2 catalyst by Eu modification for selective catalytic reduction of NOx with NH3 - Yuan-zhen Liu; Qi-yan Xu; Rui-tang Guo; Chao-peng Duan; Gui-lin Wu; Yu-fang Miao; Jing-wen Gu (Environmental Science and Pollution Research, 2020)

Role of adjuvant (chemo)radiotherapy for resected extrahepatic cholangiocarcinoma: a meta-analysis - Xin-qi Shi; Jing-yu Zhang; Hua Tian; Ling-na Tang; Ai-lin Li (Journal of Zhejiang University-SCIENCE B, 2020)

A review of progress in coupled ocean-atmosphere model developments for ENSO studies in China - Rong-Hua Zhang; Yongqiang Yu; Zhenya Song; Hong-Li Ren; Youmin Tang; Fangli Qiao; Tongwen Wu; Chuan Gao; Junya Hu; Feng Tian; Yuchao Zhu; Lin Chen; et al. (Journal of Oceanology and Limnology, 2020)

The power of habit: does production experience lead to pesticide overuse? - Yanzhong Huang; Xiaofeng Luo; Lin Tang; Weizhen Yu (Environmental Science and Pollution Research, 2020)

Short-term associations between ambient fine particulate matter pollution and hospital visits for chronic obstructive pulmonary disease in Yinzhou District, China - Cheng-yi Lin; Die Li; Jie-ming Lu; Zhe-bin Yu; Yao Zhu; Peng Shen; Meng-ling Tang; Ming-juan Jin; Hong-bo Lin; Li-ming Shui; Kun Chen; Jian-bing Wang (Environmental Science and Pollution Research, 2020)

Detection of serum IgM and IgG for COVID-19 diagnosis - Ling Zhong; Junlan Chuan; Bo Gong; Ping Shuai; Yu Zhou; Yi Zhang; Zhilin Jiang; Dingding Zhang; Xiaoqi Liu; Shi Ma; Yi Huang; He Lin; et al. (Science China Life Sciences, 2020)

An alternative splicing variant of mineralocorticoid receptor discovered in preeclampsia tissues and its effect on endothelial dysfunction - Mengxi Guo; Chengliang Zhou; Gufeng Xu; Lin Tang; Yechun Ruan; Ying Yu; Xianhua Lin; Dandan Wu; Hao Chen; Priscilla Yu; Luyang Jin; Yinyu Wang; et al. (Science China Life Sciences, 2020)

Non-motor Symptoms in Parkinson’s Disease Patients with Parkin Mutations: More Depression and Less Executive Dysfunction - Jie Song; Bo Shen; Yu-Jie Yang; Feng-tao Liu; Jue Zhao; Yi-Lin Tang; Chen Chen; Zheng-Tong Ding; Yu An; Jian-Jun Wu; Yi-Min Sun; Jian Wang (Journal of Molecular Neuroscience, 2020)

Development of Climate and Earth System Models in China: Past Achievements and New CMIP6 Results - Tianjun Zhou; Ziming Chen; Liwei Zou; Xiaolong Chen; Yongqiang Yu; Bin Wang; Qing Bao; Ying Bao; Jian Cao; Bian He; Shuai Hu; Lijuan Li; et al. (Journal of Meteorological Research, 2020)

Carbon-based magnetic nanocomposite as catalyst for persulfate activation: a critical review - Ya Pang; Kun Luo; Lin Tang; Xue Li; Jiangfang Yu; Junyuan Guo; Yuanyuan Liu; Zhu Zhang; Ran Yue; Ling Li (Environmental Science and Pollution Research, 2019)

Investigating the Transport Mechanism of PM2.5 Pollution during January 2014 in Wuhan, Central China - Miaomiao Lu; Xiao Tang; Zifa Wang; Lin Wu; Xueshun Chen; Shengwen Liang; Hui Zhou; Huangjian Wu; Ke Hu; Longjiao Shen; Jia Yu; Jiang Zhu (Advances in Atmospheric Sciences, 2019)
Severe haze pollution that occurred in January 2014 in Wuhan was investigated. The factors leading to Wuhan’s PM 2.5 pollution and the characteristics and formation mechanism were found to be significantly different from other megacities, like Beijing. Both the growth rates and decline rates of PM 2.5 concentrations in Wuhan were lower than those in Beijing, but the monthly PM 2.5 value was approximately twice that in Beijing. Furthermore, the sharp increases of PM 2.5 concentrations were often accompanied by strong winds. A high-precision modeling system with an online source-tagged method was established to explore the formation mechanism of five haze episodes. The long-range transport of the polluted air masses from the North China Plain (NCP) was the main factor leading to the sharp increases of PM 2.5 concentrations in Wuhan, which contributed 53.4% of the monthly PM 2.5 concentrations and 38.5% of polluted days. Furthermore, the change in meteorological conditions such as weakened winds and stable weather conditions led to the accumulation of air pollutants in Wuhan after the long-range transport. The contribution from Wuhan and surrounding cities to the PM 2.5 concentrations was determined to be 67.4% during this period. Under the complex regional transport of pollutants from surrounding cities, the NCP, East China, and South China, the five episodes resulted in 30 haze days in Wuhan. The findings reveal important roles played by transregional and intercity transport in haze formation in Wuhan.

A new phenolic glycoside from the Idesia polycarpa Maxim. leaves - Lei Huang; Tong Peng; Yu Li; Yunyun He; Li Wang; Shiyan Zhang; Yiran Sun; Fang Chen; Lin Tang (Natural Product Research, 2019)

Development of Multi-axis Motor Control Systems for Lower Limb Robotic Exoskeleton - Cheng-Tang Pan; Chun-Chieh Chang; Pei-Yuan Sun; Cheng-Lung Lee; Tzu-Chieh Lin; Chung-Kun Yen; Yu-Sheng Yang (Journal of Medical and Biological Engineering, 2019)

Leaf Senescence can be Induced by Inhibition of Root Respiration - Gang-liang Tang; Xiang-yi Li; Li-sha Lin; Zhu-yu Gu; Fan-jiang Zeng (Journal of Plant Growth Regulation, 2019)

Fractal characterization of sediment particle size distribution in the water-level fluctuation zone of the Three Gorges Reservoir, China - Jin-lin Li; Yu-hai Bao; Jie Wei; Xiu-bin He; Qiang Tang; Jean de Dieu Nambajimana (Journal of Mountain Science, 2019)

Pseudoxanthomonas composti sp. nov., isolated from compost - Jun Lin; Guiqin Yang; Jia Tang; Zhen Li; Zhen Yu; Li Zhuang (Antonie van Leeuwenhoek, 2019)

Diversity- and density-mediated allelopathic effects of resident plant communities on invasion by an exotic plant - Michael Opoku Adomako; Lei Ning; Min Tang; Dao-Lin Du; Mark van Kleunen; Fei-Hai Yu (Plant and Soil, 2019)

Design, synthesis and biological evaluation of novel indone derivatives as selective ERβ modulators - Xi-Xi Liu; Mei-Lin Tang; Chen Zhong; Yun Tang; Jian-Ming Yu; Xun Sun (Medicinal Chemistry Research, 2019)

Predicting the cytotoxicity of disinfection by-products to Chinese hamster ovary by using linear quantitative structure–activity relationship models - Li-Tang Qin; Xin Zhang; Yu-Han Chen; Ling-Yun Mo; Hong-Hu Zeng; Yan-Peng Liang; Hua Lin; Dun-Qiu Wang (Environmental Science and Pollution Research, 2019)

Fucoxanthin prevents lipopolysaccharide-induced depressive-like behavior in mice via AMPK- NF-κB pathway - Xi Jiang; Guokang Wang; Qian Lin; Zhihua Tang; Qizhi Yan; Xuefeng Yu (Metabolic Brain Disease, 2019)

Contamination assessment and health risk of arsenic exposure to stairway dust in the zinc smelting district, Northeast China - Na Zheng; Yan Yu; Shengnan Hou; Sujuan Xu; Lin Tang; Xiaofeng Ji (Environmental Geochemistry and Health, 2019)

Detection and genetic characterization of porcine pegivirus from pigs in China - Dan Lei; Yu Ye; Kun Lin; Fanfan Zhang; Dongyan Huang; Kai Li; Weifeng Yuan; Qiong Wu; Zhen Ding; Leyi Wang; Deping Song; Yuxin Tang (Virus Genes, 2019)

Provenance of the Langjiexue Group to the south of the Yarlung-Tsangpo Suture Zone in southeastern Tibet: Insights on the evolution of the Neo-Tethys Ocean in the Late Triassic - Da-Ren Fang; Gen-Hou Wang; Ken-ichiro Hisada; Guo-Li Yuan; Fang-Lin Han; Dian Li; Yu Tang; Qiu-Ming Pei; Liang-Liang Zhang (International Geology Review, 2019)

Soil organic carbon and total nitrogen stocks in alpine ecosystems of Altun Mountain National Nature Reserve in dry China - Zhenzhen Zhao; Xiangfeng Zhang; Shikui Dong; Yu Wu; Shiliang Liu; Xukun Su; Xuexia Wang; Yong Zhang; Lin Tang (Environmental Monitoring and Assessment, 2019)

EGb761 improves the cognitive function of elderly db/db−/− diabetic mice by regulating the beclin-1 and NF-κB signaling pathways - Zhu-Fei Guan; Xiao-Ming Zhang; Ying-Hong Tao; Yu Zhang; Yan-Yan Huang; Gang Chen; Wei-Jun Tang; Gang Ji; Qi-Lin Guo; Ming Liu; Qian Zhang; Na-Na Wang; et al. (Metabolic Brain Disease, 2018)

Insights into the role of extracellular polymeric substances in Zn2+ adsorption in different biological sludge systems - Yu-Xia Song; Cheng-Hai Lu; Peng Liu; Xi-Lin Chai; Xi Chen; Xiao-Bo Min; Chong-Jian Tang; Li-Yuan Chai (Environmental Science and Pollution Research, 2018)

Acute effect of fine and coarse particular matter on cardiovascular visits in Ningbo, China - Pei-wen Zheng; Peng Shen; Zhen-hua Ye; Zhen-yu Zhang; Peng-fei Chai; Die Li; Ming-juan Jin; Meng-Ling Tang; Huai-chu Lu; Hong-bo Lin; Jian-bing Wang; Kun Chen (Environmental Science and Pollution Research, 2018)

PEGylated lipid microspheres loaded with cabazitaxel for intravenous administration: stability, bioavailability, antitumor efficacy, and toxicity - Yang Liu; Bin Xie; Lin Li; Xinyu Zhang; Yu Zhang; Haibing He; Tian Yin; Xing Tang; Cuifang Cai; Jingxin Gou (Drug Delivery and Translational Research, 2018)

Expression of BC1 Impairs Spatial Learning and Memory in Alzheimer’s Disease Via APP Translation - Tongmei Zhang; Pei Pang; Zemin Fang; Yu Guo; Hao Li; Xinyan Li; Tian Tian; Xin Yang; Wenting Chen; Shu Shu; Na Tang; Jianhua Wu; et al. (Molecular Neurobiology, 2018)

Physical Stability of Amorphous Solid Dispersions: a Physicochemical Perspective with Thermodynamic, Kinetic and Environmental Aspects - Xia Lin; Yang Hu; Lei Liu; Lili Su; Na Li; Jing Yu; Bo Tang; Ziyi Yang (Pharmaceutical Research, 2018)

Converting natural evergreen broadleaf forests to intensively managed moso bamboo plantations affects the pool size and stability of soil organic carbon and enzyme activities - Ziwen Lin; Yongfu Li; Caixian Tang; Yu Luo; Weijun Fu; Xiaoqing Cai; Yongchun Li; Tian Yue; Peikun Jiang; Shuaidong Hu; Scott X. Chang (Biology and Fertility of Soils, 2018)

Sorption-desorption behaviors of heavy metals by biochar-compost amendment with different ratios in contaminated wetland soil - Zhaoxue Yang; Jie Liang; Lin Tang; Guangming Zeng; Man Yu; Xiaodong Li; Xuemei Li; Yingying Qian; Haipeng Wu; Yuan Luo; Dan Mo (Journal of Soils and Sediments, 2018)

Correction to: Age at menarche and age at natural menopause in East Asian women: a genome-wide association study - Jiajun Shi; Ben Zhang; Ji-Yeob Choi; Yu-Tang Gao; Huaixing Li; Wei Lu; Jirong Long; Daehee Kang; Yong-Bing Xiang; Wanqing Wen; Sue K. Park; Xingwang Ye; et al. (GeroScience, 2018)

Spatiotemporal expression of proprotein convertase subtilisin/kexin type 5 in the development of anorectal malformations in fetal rats - Xiao Bing Tang; Li Chen; Wei Lin Wang; Zheng Wei Yuan; Yu Zuo Bai (Journal of Molecular Histology, 2017)

Air pollution and hospital visits for acute upper and lower respiratory infections among children in Ningbo, China: A time-series analysis - Pei-wen Zheng; Jian-bing Wang; Zhen-yu Zhang; Peng Shen; Peng-fei Chai; Die Li; Ming-juan Jin; Meng-Ling Tang; Huai-chu Lu; Hong-bo Lin; Kun Chen (Environmental Science and Pollution Research, 2017)

Identification and expression patterns of 20-hydroxyecdysone-responsive genes from Procambarus clarkii - Bao-Jian Zhu; Lin Tang; Ying-Ying Yu; Dao-Jun Wang; Chao-Liang Liu (Genes & Genomics, 2017)

The Chlorophyll a Fluorescence Characteristic in Different Types of Leaf Senescence in Alhagi sparsifolia - Gang-Liang Tang; Xiang-Yi Li; Li-Sha Lin; Zhu-Yu Gu; Fan-Jiang Zeng (Journal of Plant Growth Regulation, 2016)

Research on China export structure adjustment: an embodied carbon perspective - Pi-qin Gong; Bao-jun Tang; Yu-chong Xiao; Gao-jie Lin; Jian-yun Liu (Natural Hazards, 2016)

Protective Effects of Chinese Herbal Medicine Rhizoma drynariae in Rats After Traumatic Brain Injury and Identification of Active Compound - Wenzhu Wang; Haigang Li; Jintao Yu; Michael Hong; Jing Zhou; Lin Zhu; Yang Wang; Min Luo; Zian Xia; Zeng-Jin Yang; Tao Tang; Ping Ren; et al. (Molecular Neurobiology, 2016)

Investigation of peat sediments from Daiyun Mountain in southeast China: late Holocene vegetation, climate and human impact - Lin Zhao; Chunmei Ma; Lingyu Tang; Kam-biu Liu; Limi Mao; Yu Zhang; Huayu Lu; Shuangye Wu; Qingyun Tu (Vegetation History and Archaeobotany, 2016)

The Association Between Serum Selenium Levels with Rheumatoid Arthritis - Na Yu; Fang Han; Xiaojun Lin; Chun Tang; Jinghua Ye; Xiaoyan Cai (Biological Trace Element Research, 2016)

Molecular phylogenetic analysis of key Jatropha species inferred from nrDNA ITS and chloroplast (trnL-F and rbcL) sequences - Guo-ye Guo; Sheng-hua Wang; Ying Xu; Lin Tang; Mao-qun Yu; Fang Chen (Genes & Genomics, 2016)

Knockdown of hippocampal cysteinyl leukotriene receptor 1 prevents depressive behavior and neuroinflammation induced by chronic mild stress in mice - Xu-Ben Yu; Rong-Rong Dong; Hui Wang; Jing-Ran Lin; Yun-Qi An; Yong Du; Su-Su Tang; Mei Hu; Yan Long; Hong-Bin Sun; Ling-Yi Kong; Hao Hong (Psychopharmacology, 2016)

Infralimbic Endothelin1 Is Critical for the Modulation of Anxiety-Like Behaviors - Lin-Lin Bi; Ming Chen; Lei Pei; Shu Shu; Hui-Juan Jin; Hong-Lin Yan; Na Wei; Shan Wang; Xin Yang; Huan-Huan Yan; Meng-meng Xu; Cheng-Ye Yao; et al. (Molecular Neurobiology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Vascular endothelial growth factor-C protects heart from ischemia/reperfusion injury by inhibiting cardiomyocyte apoptosis - Xu-guang Chen; Yan-xia Lv; Dan Zhao; Lei Zhang; Fei Zheng; Jian-Ye Yang; Xiao-lin Li; Lu Wang; Lin-Yun Guo; Ya-mu Pan; Yu-wen Yan; Shi-You Chen; et al. (Molecular and Cellular Biochemistry, 2016)

Erratum to: Identification of the Avulsion-Injured Spinal Motoneurons - Min Tan; Ming-zhou Yuan; Tian-yu Sun; Ying-yu Xie; Lin-Lin Liu; Ying Tang; Ze-min Ling; Ying-qin Li; Guang-yin Yu; Li Hua Zhou (Journal of Molecular Neuroscience, 2016)

Association between occupational stressors and type 2 diabetes among Chinese police officers: a 4-year follow-up study in Tianjin, China - Hao Yu; Jin-chuan Liu; Ya-jiao Fan; Chen Li; Li-xin Zhang; Xi Chen; Song Yue; Wen-li Lu; Xi-lin Yang; Nai-jun Tang (International Archives of Occupational and Environmental Health, 2016)

Physiological and proteomic analysis in two wild tomato lines under waterlogging and high temperature stress - Hsin-Hung Lin; Kuan-Hung Lin; Jia-Yu Syu; Shun-Yuan Tang; Hsiao-Feng Lo (Journal of Plant Biochemistry and Biotechnology, 2016)

New Perspectives on Dietary-derived Treatments and Food Safety—Antinomy in a New Era - Si-Yuan Pan; Si-Hua Gao; Rui-Chao Lin; Shu-Feng Zhou; Hong-Guan Dong; Min-Ke Tang; Zhi-Ling Yu; Kam-Ming Ko (Critical Reviews in Food Science and Nutrition, 2015)

A Uniform Ultra-Small Microsphere/SAIB Hybrid Depot with Low Burst Release for Long-Term Continuous Drug Release - Xia Lin; Yuhong Xu; Xing Tang; Yan Zhang; Jian Chen; Yu Zhang; Haibing He; Ziyi Yang (Pharmaceutical Research, 2015)

Voriconazole: a novel treatment option for cryptococcal meningitis - Yan Yao; Jia-Tang Zhang; Bo Yan; Ting Gao; Xiao-Wei Xing; Cheng-Lin Tian; Xu-Sheng Huang; Sheng-Yuan Yu (Infectious Diseases, 2015)

Intra-Colonial Functional Differentiation-Related Modulation of the Cellular Membrane in a Pocilloporid Coral Seriatopora caliendrum - Chuan-Ho Tang; Ping-Chang Ku; Ching-Yu Lin; Te-Hao Chen; Kuo-Hsin Lee; Shu-Hui Lee; Wei-Hsien Wang (Marine Biotechnology, 2015)

Identification of the Avulsion-Injured Spinal Motoneurons - Min Tan; Ming-zhou Yuan; Tian-yu Sun; Ying-yu Xie; Lin-Lin Liu; Ying Tang; Ze-min Ling; Ying-qin Li; Guang-yin Yu; Li Hua Zhou (Journal of Molecular Neuroscience, 2015)

High-level expression and characterization of a thermophilic β-mannanase from Aspergillus niger in Pichia pastoris - Shi Yu; Zhezhe Li; Yaping Wang; Wanping Chen; Lin Fu; Wei Tang; Chen Chen; Yunyun Liu; Xue Zhang; Lixin Ma (Biotechnology Letters, 2015)

Eutrophic water purification efficiency using a combination of hydrodynamic cavitation and ozonation on a pilot scale - Wei-Xin Li; Chuan-Dong Tang; Zhi-Lin Wu; Wei-Min Wang; Yu-Feng Zhang; Yi Zhao; Giancarlo Cravotto (Environmental Science and Pollution Research, 2015)

Regional response of dengue fever epidemics to interannual variation and related climate variability - Chung-Min Liao; Tang-Luen Huang; Yi-Jun Lin; Shu-Han You; Yi-Hsien Cheng; Nan-Hung Hsieh; Wei-Yu Chen (Stochastic Environmental Research and Risk Assessment, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Impacts of uncertainty in AVOC emissions on the summer ROx budget and ozone production rate in the three most rapidly-developing economic growth regions of China - Feng Wang; Junling An; Ying Li; Yujia Tang; Jian Lin; Yu Qu; Yong Chen; Bing Zhang; Jing Zhai (Advances in Atmospheric Sciences, 2014)

Inhibition of acid-sensing ion channel 1a in hepatic stellate cells attenuates PDGF-induced activation of HSCs through MAPK pathway - Fan-rong Wu; Chun-xiao Pan; Chao Rong; Quan Xia; Feng-lai Yuan; Jie Tang; Xiao-yu Wang; Nan Wang; Wen-lin Ni; Fei-hu Chen (Molecular and Cellular Biochemistry, 2014)

Temporal and spatial expression of caudal-type homeobox gene-2 during hindgut development in rat embryos with ethylenethiourea-induced anorectal malformations - Xiao Bing Tang; Tao Zhang; Wei Lin Wang; Zheng Wei Yuan; Yu Zuo Bai (Cell and Tissue Research, 2014)

Cingulum Correlates of Cognitive Functions in Patients with Mild Cognitive Impairment and Early Alzheimer’s Disease: A Diffusion Spectrum Imaging Study - Yi-Cheng Lin; Yao-Chia Shih; Wen-Yih I. Tseng; Yu-Hsiu Chu; Meng-Tien Wu; Ta-Fu Chen; Pei-Fang Tang; Ming-Jang Chiu (Brain Topography, 2014)

Microbiota Regulates the TLR7 Signaling Pathway Against Respiratory Tract Influenza A Virus Infection - Sha Wu; Zhen-You Jiang; Yi-Fan Sun; Bin Yu; Jia Chen; Cong-Qi Dai; Xian-Lin Wu; Xiao-Long Tang; Xiao-Yin Chen (Current Microbiology, 2013)

Transgenic expression of an insect diapause-specific peptide (DSP) in Arabidopsis resists phytopathogenic fungal attacks - Tingquan Wu; Yongfang Chen; Weida Chen; Shenghao Zou; Yongqing Zhang; Yu’e Lin; Zhaojun Liang; Dingzhong Tang (European Journal of Plant Pathology, 2013)

Activating transcription factor 4 is involved in endoplasmic reticulum stress-mediated apoptosis contributing to vascular calcification - Xiao-Hui Duan; Jin-Rui Chang; Jing Zhang; Bao-Hong Zhang; Yu-Lin Li; Xu Teng; Yi Zhu; Jie Du; Chao-Shu Tang; Yong-Fen Qi (Apoptosis, 2013)

The enhancement of biofilm formation in Group B streptococcal isolates at vaginal pH - Yueh-Ren Ho; Chien-Ming Li; Chen-Hsiang Yu; Yuh-Jyh Lin; Ching-Ming Wu; I-Chen Harn; Ming-Jer Tang; Yi-Ting Chen; Fang-Chi Shen; Chien-Yi Lu; Tai-Chun Tsai; Jiunn-Jong Wu (Medical Microbiology and Immunology, 2013)

Quantitative evaluation of Candia antarctica lipase B displayed on the cell surface of a Pichia pastoris based on an FS anchor system - Xing-xiang Liang; Bei-bei Wang; Yu-fei Sun; Ying Lin; Shuang-yan Han; Sui-ping Zheng; Tang-bing Cui (Biotechnology Letters, 2013)

Tenuibacillus halotolerans sp. nov., a novel bacterium isolated from a soil sample from a salt lake in Xinjiang, China and emended description of the genus Tenuibacillus - Xu-Hong Gao; Sheng Gao; Yu Zhou; Hui-Lin Guan; Yun-Jiao Zhang; Man Jia; Hua-Wei Huang; Dong-Xu Yang; Wen-Jun Li; Shu-Kun Tang (Antonie van Leeuwenhoek, 2013)

Effects of Sub-soil Drip Fertigation on Sugarcane in Field Conditions - Gui-Fen Chen; Qi-Zhan Tang; Yang-Rui Li; Yu-Yi Huang; Bin Liu; Lin Xu; Hai-Rong Huang (Sugar Tech, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

miR-15b and miR-16 regulate TNF mediated hepatocyte apoptosis via BCL2 in acute liver failure - Fangmei An; Bangdong Gong; Hui Wang; Dongshan Yu; Gangde Zhao; Lanyi Lin; Weiliang Tang; Hong Yu; Shisan Bao; Qing Xie (Apoptosis, 2012)

Diversity of potential pathogenicity and biofilm formation among Burkholderia cepacia complex water, clinical, and agricultural isolates in China - Muhammad Ibrahim; Qiaomei Tang; Yu Shi; Abdulwareth Almoneafy; Yuan Fang; Liuhu Xu; Wen Li; Bin Li; Guan-Lin Xie (World Journal of Microbiology and Biotechnology, 2012)

Effects of isoflurane exposure during pregnancy on postnatal memory and learning in offspring rats - Fei-juan Kong; Yu-wen Tang; Ai-fei Lou; Hong Chen; Lin-hao Xu; Xiao-ming Zhang; Hui-shun Lu (Molecular Biology Reports, 2012)

Identification of secretory gelsolin as a plasma biomarker associated with distant organ metastasis of colorectal cancer - Ming-Hung Tsai; Chih-Ching Wu; Pei-Hua Peng; Ying Liang; Yung-Chin Hsiao; Kun-Yi Chien; Jeng-Ting Chen; Shin-Jie Lin; Rei-Ping Tang; Ling-Ling Hsieh; Jau-Song Yu (Journal of Molecular Medicine, 2012)

Matrix metalloproteinase-9 as new biomarkers of severity in multiple organ dysfunction syndrome caused by trauma and infection - Lin Teng; Min Yu; Jun-ming Li; Hua Tang; Jing Yu; Li-hua Mo; Jing Jin; Xian-zhe Liu (Molecular and Cellular Biochemistry, 2012)

Dexamethasone attenuates development of monocrotaline-induced pulmonary arterial hypertension - Wei Wang; Yu-lin Wang; Xiao-ying Chen; Yu-tang Li; Wei Hao; You-peng Jin; Bo Han (Molecular Biology Reports, 2011)

The mechanisms underlying ICa heterogeneity across murine left ventricle - Lin Xu; Xu-Yong Li; Yu Liu; Hai-Tao Li; Jing Chen; Xiao-Yan Li; Xue-Jun Jiang; Gang Wu; Yan-Hong Tang; Xi Wang; Cong-Xin Huang (Molecular and Cellular Biochemistry, 2011)

Monitoring and identification of spatiotemporal landscape changes in multiple remote sensing images by using a stratified conditional Latin hypercube sampling approach and geostatistical simulation - Yu-Pin Lin; Hone-Jay Chu; Yu-Long Huang; Chia-Hsi Tang; Shahrokh Rouhani (Environmental Monitoring and Assessment, 2011)

Bioavailability Study of Berberine and the Enhancing Effects of TPGS on Intestinal Absorption in Rats - Wei Chen; Yu-Qiang Miao; Dong-Jiao Fan; Shen-Shen Yang; Xia Lin; Ling-Kuo Meng; Xing Tang (AAPS PharmSciTech, 2011)

Phylogeny of Arachis based on internal transcribed spacer sequences - Chuan Tang Wang; Xiu Zhen Wang; Yue Yi Tang; Dian Xu Chen; Feng Gao Cui; Jian Cheng Zhang; Shan Lin Yu (Genetic Resources and Crop Evolution, 2011)

Identification of the VP92R gene from infectious spleen and kidney necrosis virus - Xiaopeng Xu; Qingxia Lu; Rui Wang; Ting Lin; Shaoping Weng; Ling Lu; Zhongsheng Li; Xiaoqiang Yu; Junliang Tang; Jianguo He (Virus Genes, 2010)

Relation of uric acid levels to aortic root dilatation in hypertensive patients with and without metabolic syndrome - Li-jiang Tang; Jian-jun Jiang; Xiao-feng Chen; Jian-an Wang; Xian-fang Lin; Yu-xi Du; Cong-feng Fang; Zhao-xia Pu (Journal of Zhejiang University-SCIENCE B, 2010)

Genetic analysis of the VP1 region of enterovirus 71 reveals the emergence of genotype A in central China in 2008 - Haiyang Yu; Wei Chen; Hongwei Chang; Renshu Tang; Jun Zhao; Lin Gan; Boyu Liu; Jason Chen; Mingli Wang (Virus Genes, 2010)

Over-expression of the AtGA2ox8 gene decreases the biomass accumulation and lignification in rapeseed (Brassica napus L.) - Xiao-ying Zhao; Deng-feng Zhu; Bo Zhou; Wu-sheng Peng; Jian-zhong Lin; Xing-qun Huang; Re-qing He; Yu-hong Zhuo; Dan Peng; Dong-ying Tang; Ming-fang Li; Xuan-ming Liu (Journal of Zhejiang University-SCIENCE B, 2010)

Porcine lactoferrin as feedstuff additive elevates avian immunity and potentiates vaccination - Che-Ming Hung; Shinn-Chih Wu; Chih-Ching Yen; Ming-Fong Lin; Yi-Wen Lai; Yu-Tang Tung; Hsiao-Ling Chen; Chuan-Mu Chen (BioMetals, 2010)

A Non-fluorescent Derivative from Derivatizing trans, trans-Muconic Acid with 2-(2-Naphthoxy)ethyl-2-(piperidino)ethanesulfonate - Tang-Chia Chung; Wung-Pung Su; Hwang-Shang Kou; Yu-Ting Lin; Min-Yuan Hung; Hsin-Lung Wu (Journal of Fluorescence, 2010)

Ploidy doubling by in vitro culture of excised protocorms or protocorm-like bodies in Phalaenopsis species - Wen Huei Chen; Ching Yan Tang; Yu Lin Kao (Plant Cell, Tissue and Organ Culture (PCTOC), 2009)

Transcriptional analysis of the hsp70 gene in a haloarchaeon Natrinema sp. J7 under heat and cold stress - Hao Zhang; Peng Cui; Lu Lin; Ping Shen; Bing Tang; Yu-Ping Huang (Extremophiles, 2009)

Digenic inheritance of non-syndromic deafness caused by mutations at the gap junction proteins Cx26 and Cx31 - Xue-Zhong Liu; Yongyi Yuan; Denise Yan; Emilie Hong Ding; Xiao Mei Ouyang; Yu Fei; Wenxue Tang; Huijun Yuan; Qing Chang; Li Lin Du; Xin Zhang; Guojian Wang; et al. (Human Genetics, 2009)

The impact of chemical lateral boundary conditions on CMAQ predictions of tropospheric ozone over the continental United States - Youhua Tang; Pius Lee; Marina Tsidulko; Ho-Chun Huang; Jeffery T. McQueen; Geoffrey J. DiMego; Louisa K. Emmons; Robert B. Pierce; Anne M. Thompson; Hsin-Mu Lin; Daiwen Kang; Daniel Tong; et al. (Environmental Fluid Mechanics, 2009)

Impact of consistent boundary layer mixing approaches between NAM and CMAQ - Pius Lee; Youhua Tang; Daiwen Kang; Jeff McQueen; Marina Tsidulko; Ho-Chun Huang; Sarah Lu; Mary Hart; Hsin-Mu Lin; Shaocai Yu; Geoff DiMego; Ivanka Stajner; et al. (Environmental Fluid Mechanics, 2009)

Identification of a Kunitz inhibitor from Albizzia kalkora and its inhibitory effect against pest midgut proteases - Jia-Yu Zhou; Hai Liao; Nian-Hui Zhang; Lin Tang; Ying Xu; Fang Chen (Biotechnology Letters, 2008)

Cloning, Structure, and Expression Pattern of the P-450 Aromatase Gene in Rice Field Eel (Monopterus albus) - Ju-Hua Yu; Yong-Kai Tang; Jian-Lin Li (Biochemical Genetics, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Streptomyces serianimatus sp. nov., isolated from a rhizophere soil - Yong-Xia Wang; Xiao-Yang Zhi; Hua-Hong Chen; Yu-Qin Zhang; Shu Kun Tang; Cheng-Lin Jiang; Li-Hua Xu; Wen-Jun Li (Antonie van Leeuwenhoek, 2007)

MHC-BPS: MHC-binder prediction server for identifying peptides of flexible lengths from sequence-derived physicochemical properties - Juan Cui; Lian Yi Han; Hong Huang Lin; Zhi Qun Tang; Li Jiang; Zhi Wei Cao; Yu Zong Chen (Immunogenetics, 2006)

Pilot-Scale Fermentation and Purification of the Recombinant Allophycocyanin Over-Expressed in Escherichia coli - Baosheng Ge; Zhihong Tang; Liping Lin; Yuhong Ren; Yu Yang; Song Qin (Biotechnology Letters, 2005)

Study on construction of cDNA libraries from rat normal liver and regeneration liver with smart technique - Lin Jun-Tang; Wang Cong-Rui; Jogenananda Pramanik; Zhang Hui-Yong; Feng Hui-Gen; Yang Bao-Sheng; L. I. Yu-Chang; Xu Cun-Shuan (Indian Journal of Clinical Biochemistry, 2004)

Cloning and expression of a new Tibetan hulless barley (Hordeum vulgare) β-1,3-glucanase gene - Zeng Yu; Xu Ying; Tang Lin; Qiang Xiao-Lin; Chen Fang (Biotechnology Letters, 2003)